Porous electrodes for electrochemical devices
By using porous electrodes and dielectric layers with porosity greater than 30% by volume % in lithium-ion batteries, the problems of low reliability and fire risk in existing lithium-ion batteries at high temperatures are solved, and higher mechanical stability and safety are achieved sex.
Patent Information
- Application Number
- CN201980029285.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-05-07
- Filing Date
- 2019-05-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2039-05-06
AI Technical Summary
Existing lithium-ion batteries exhibit low reliability and risk of fire at high temperatures, and the use of organic binders leads to increased series resistance and insufficient mechanical stability of the battery.
Using porous electrodes with a porosity greater than 30 volume % porosity, the aggregates or agglomerates of nanoparticles are prepared by electrophoresis, avoiding the use of organic binders, and depositing dielectric layers on the electrode surface to reduce interfacial reactions.
A porous electrode that operates at high temperatures without reliability problems is realized, reducing the interface resistance of the battery, improving mechanical stability, and reducing the risk of fire.
Smart Images

Figure CN112088450B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemistry, in particular to electrochemical systems, and more particularly to thin-layer electrochemical systems. More precisely, the present invention relates to electrodes that can be used in electrochemical systems such as high-power batteries (especially lithium-ion batteries), supercapacitors, fuel cells and photovoltaic cells. The electrodes are suitable for use as anodes and cathodes. The present invention relates to porous electrodes; these porous electrodes can be impregnated with a liquid electrolyte.
[0002] The invention also relates to a method for preparing such a porous electrode using nanoparticles of electrode material, preferably in the form of a thin layer, and to the electrode obtained thereby. The invention also relates to a method for manufacturing an electrochemical device comprising at least one of these electrodes, and to the device obtained thereby. Background Art
[0003] There are several technologies for storing electrical energy, and the choice for a given application depends most importantly on the power requirements (expressed in W) and the energy requirements (expressed in Wh). For example, if high power is desired in a relatively short time, a capacitor or supercapacitor may be a good solution. A capacitor or supercapacitor consists of two porous electrodes separated by an insulating membrane (usually made of activated carbon to ensure good electronic conductivity); the electrodes are immersed in an electrolyte, which forms a double layer on the electrode surface capable of storing electrical energy. These devices are characterized by very short charge and discharge times.
[0004] The storage of electrical energy used in electric vehicles, mobile phones or computers must meet different requirements, namely to provide high power for a considerable period of time. For this reason, lithium-ion batteries are often used. Lithium-ion batteries comprise a positive electrode, an electrolyte and a negative electrode. During the operation of a lithium-ion battery, lithium ions migrate from one electrode through the electrolyte and reach the other electrode. During the discharge of the battery, a certain amount of lithium from the electrolyte reacts with the positive electrode active material and an equal amount of lithium ions is introduced into the electrolyte by the negative electrode active material, so that the concentration of lithium ions in the electrolyte remains constant. The insertion of lithium in the material forming the electrode is counteracted by the supply of electrons by the negative electrode via an external circuit; the battery can therefore supply an electric current. During charging, the opposite phenomenon occurs.
[0005] The power density of lithium-ion batteries is generally lower than that of supercapacitors due to the slower diffusion of lithium ions in the thickness of the active material (electrodes, electrolyte) and the migration time of lithium ions in the electrolyte. The storage capacity of a lithium-ion battery depends on its electrodes, among other factors, especially on the amount of active material present in the electrodes and, to a lesser extent, on the thickness of the electrodes; when density and surface are the same, the thicker the electrodes, the higher the energy storage capacity of the battery. However, as the thickness of the layer increases, the internal resistance (series resistance) of the battery increases.
[0006] In order to exceed the performance of conventional lithium-ion batteries, people are looking for materials with high storage capacity and high charge and discharge power. More precisely, batteries with high energy density, high power density and long life (expressed in calendar life and number of charge and discharge cycles) are desired; for some applications, people are looking for batteries that can work well at low temperatures (it is known that the series resistance inside the battery increases when the temperature drops). In addition, considering the large amount of energy that can be stored, the battery must not pose a safety hazard in the event of a failure; for example, the battery must not catch fire. Finally, the various components of the lithium battery must be selected in such a way that a low-cost battery can be manufactured by a reliable and inexpensive method.
[0007] Known electrochemical cells include, for example, lithium-ion batteries, which use particles of electrode active materials of microscopic size connected by organic binders. Patent document WO 02 / 075 826 discloses an electrode for an electrochemical cell comprising an electrode material having a mesoporous structure and an organic binder. Since the organic binder is an electrical insulator, it is embedded with carbon particles as an electronic conductor. These electrodes include a three-dimensional mesoporous structure that can be impregnated with an electrolyte to form a junction with a large specific surface area. The three-dimensional structure of the electrode makes it possible to overcome the problem of ion diffusion in the electrolyte inherent in conventional electrodes with a large active surface area, and ensures interconnectivity and the entry of liquid organic electrolytes into all porous spaces. The mechanical stability of the structure is basically provided by the organic binder in the mesoporous electrode.
[0008] In the electrodes described in patent document WO 02 / 075 826, the presence of an organic binder is an important feature, but it has several disadvantages. The organic binder embedded with conductive particles can cause failures during thermal cycling; the electrode material particles connected together by the organic binder can locally lose electrical contact, resulting in a gradual increase in the series resistance of the battery. The presence of an organic binder also limits the operating temperature of the battery and there is also a risk of fire.
[0009] Finally, the presence of organic binders may be incompatible with certain manufacturing methods, in particular those involving vacuum deposition and / or high temperature deposition. In particular, the presence of organic binders makes it impossible to use the subsequent deposition of dielectric layers by atomic layer deposition (ALD) because there is a risk that the binder will decompose during the deposition process and contaminate the ALD reactor. In addition, the presence of binders prevents the coating made by ALD from being a conformal coating and from performing its function, i.e., hindering the side reactions that may occur between the electrode and the electrolyte. However, these depositions by ALD contribute to the long life of these electrodes, not to mention the resistance of the battery comprising these electrodes over time. The presence of organic binders in the battery prevents the packaging of the battery in an optimal manner.
[0010] Furthermore, these electrochemical cells, such as lithium-ion cells, often use electrolytes containing more than 50% by weight of solvents, which can present a safety risk in the event of a malfunction; these cells can catch fire.
[0011] The present invention seeks to overcome at least some of the disadvantages of the prior art listed above.
[0012] More specifically, the problem that the present invention seeks to solve is to provide a method for manufacturing porous electrodes with controlled pore density, which method is simple, safe, fast and easy to implement, inexpensive and can overcome the use of organic binders and / or conductive materials such as graphite.
[0013] The present invention also aims to propose such a safe porous electrode, which has high ionic conductivity, a stable mechanical structure, good mechanical stability and a long service life.
[0014] Another object of the invention is to propose an electrode for a battery that is able to operate at high temperatures without reliability problems and without the risk of fire.
[0015] Another object of the present invention is to provide such a porous electrode which, in addition to having the aforementioned characteristics, also has lower interface resistance.
[0016] Another object of the present invention is to provide such a porous electrode which, in addition to having the aforementioned characteristics, is also easily wetted and impregnated by an ionic liquid.
[0017] Another object of the present invention is to propose a porous electrode impregnated with an electrolyte whose side reactions are reduced to a minimum.
[0018] Another object of the present invention is to provide a method for manufacturing an electronic, electrical or electrotechnical device such as a battery, a capacitor, a supercapacitor, a photovoltaic cell comprising the porous electrode according to the present invention.
[0019] Yet another object of the present invention is to propose devices such as batteries, lithium-ion batteries, capacitors, supercapacitors, photovoltaic cells, which are able to store high energy density, store this energy again at very high power density (especially in capacitors and supercapacitors), withstand high temperatures, have a long service life, and can be encapsulated by coatings deposited by ALD at high temperatures. Summary of the invention
[0020] Purpose of the Invention
[0021] According to the invention, the problem is solved by using at least one electrode with a porous structure, wherein the porous structure has a porosity greater than 30% by volume. Very preferably, the porosity is a mesoporosity. The electrode can be deposited by electrophoresis from a colloidal suspension of nanoparticles of the electrode material. Preferably, the electrode does not contain any binder. According to an important feature of the invention, the suspension contains aggregates or agglomerates of nanoparticles.
[0022] A first object of the present invention is a method for manufacturing a porous electrode, preferably in the form of a thin layer, comprising a layer deposited on a substrate, said layer being binder-free and having a porosity greater than 30% by volume and having pores with an average diameter of less than 50 nm, said method being characterized in that:
[0023] (a) providing a colloidal suspension comprising aggregates or agglomerates of nanoparticles of at least one material P, wherein the average primary diameter D of the nanoparticles is 50 Less than or equal to 80nm, preferably less than or equal to 50nm, the average diameter of the aggregates or agglomerates is 80nm to 300nm (preferably 100nm to 200nm),
[0024] (b) providing a substrate,
[0025] (c) depositing a porous electrode layer, preferably a mesoporous electrode layer, on the substrate from the colloidal suspension provided in step (a) by electrophoresis, by inkjet printing (hereinafter referred to as "inkjet"), by doctor blade coating (hereinafter referred to as "doctor blade"), by roller coating, by curtain coating or by dip coating,
[0026] (d) drying the layer obtained in step (c), preferably in a gas stream.
[0027] The order of steps (a) and (b) is not important.
[0028] After step (d), step (e) may be added, in which the porous electrode layer (preferably a mesoporous electrode layer) obtained in step (d) is consolidated by pressing and / or heat treatment (i.e., heating). A heat treatment step may be added after step (d), and a pressurization step may be performed before the heat treatment step to improve the performance of the obtained electrode. Depending on the material used, the heat treatment (i.e., heating) may improve the texture of the layer, improve the crystalline state of the layer, improve the sintering of the nanoparticles, or improve the adhesion of the layer to the substrate. By heat treating the porous electrode layer obtained from the colloidal suspension of aggregated nanoparticles, the agglomeration of the nanoparticles is facilitated, i.e., a strong bond is formed between these nanoparticles. Heat treatment may also be performed while applying pressure.
[0029] Advantageously, in step (c), the electrophoretic deposition is carried out by steady-state galvanostatic electrodeposition or by pulsed-mode galvanostatic electrodeposition.
[0030] Advantageously, the total porosity of the porous electrode does not exceed 50% by volume. Advantageously, the average diameter of the pores is from 2 nm to 80 nm, preferably from 2 nm to 50 nm, preferably from 6 nm to 30 nm, even more preferably from 8 nm to 20 nm.
[0031] In one embodiment of the method:
[0032] (a1) providing a colloidal suspension comprising nanoparticles of at least one material P, wherein the primary diameter of the nanoparticles is D 50 Less than or equal to 80nm, preferably less than or equal to 50nm, preferably monodisperse nanoparticles;
[0033] (a2) destabilizing the nanoparticles, preferably monodisperse nanoparticles, present in the colloidal suspension to form aggregates or agglomerates of particles having an average diameter of 80 nm to 300 nm, preferably 100 nm to 200 nm, preferably by adding a destabilizing agent such as a salt, preferably LiOH;
[0034] (b) providing a substrate;
[0035] (c) depositing a porous electrode layer on said substrate from said colloidal suspension comprising aggregates or agglomerates of nanoparticles obtained in step (a2) by electrophoresis, by inkjet, by doctor blade, by roller coating, by curtain coating or by dip coating;
[0036] (d) drying the layer, preferably in a stream of air,
[0037] And after step (d), a step (e) of consolidating the porous electrode layer obtained in step (d) may be added, such as a pressing and / or heat treatment (i.e., heating) step, preferably a heat treatment step, and a pressurizing step may be performed before step (e) to improve the performance of the obtained electrode. Heat treatment may also be performed while applying pressure.
[0038] The order of steps (a1) and (b) is not important.
[0039] Advantageously, the thickness of the deposition, preferably electrophoretic deposition, obtained in step (c) is less than 10 μm, preferably less than 8 μm, even more preferably between 1 μm and 6 μm.
[0040] The primary nanoparticles forming aggregates or agglomerates are preferably monodisperse, i.e., their primary diameters have a narrow distribution. This enables better control of porosity. Advantageously, the diameter of the nanoparticles is from 10 nm to 50 nm, preferably from 10 nm to 30 nm.
[0041] The heat treatment causes partial agglomeration of the nanoparticles of the material P (known as necking), which is beneficial to the electron conduction between the nanoparticles. It is known that the nanoparticles have a high surface energy, which is the driving force for the structural improvement; this structural improvement occurs at a temperature far below the melting point of the material and after a very short treatment time. A three-dimensional porous structure is thus formed in which the mobility of lithium ions is not reduced by grain boundaries or binder layers. This partial agglomeration of aggregated nanoparticles enables the conversion of aggregates into agglomerates. The partial agglomeration of agglomerated nanoparticles induced by the heat treatment consolidates the three-dimensional mesoporous structure.
[0042] Furthermore, electronic conduction can also be provided by the electrolyte impregnated in the electrode according to the invention. The structure also has good layer mechanical strength.
[0043] If the suspension is not sufficiently purified, aggregates or agglomerates may be obtained directly after the hydrothermal synthesis: the ionic strength of the suspension then leads to aggregation or agglomeration of the primary nanoparticles to form aggregated or agglomerated particles of larger size.
[0044] In a specific embodiment, after step (d) or step (e), in step (f), an electrically insulating material layer is preferably deposited on the pores of the porous layer, preferably the mesoporous layer, or inside the pores by atomic layer deposition ALD. The electrically insulating material can be selected from Al2O3, SiO2, ZrO2. The thickness of this covering coating is generally 1nm to 5nm. The covering coating can reduce the interfacial Faraday reaction between the porous electrode layer and the electrolyte. These layers can also be deposited by a chemical solution called CSD (acronym, Chemical Solution Deposition).
[0045] Alternatively, after step (d) or step (e), in step (f), preferably by ALD or by CSD, a layer of ion-conducting material is deposited on or inside the pores of the porous layer, preferably the mesoporous layer, and the ion-conducting material is selected from Li3PO4, Li3BO3, lithium lanthanum zirconium oxide, preferably Li7La3Zr2O 12 The thickness of the covering layer is usually 1 nm to 5 nm.
[0046] Another object of the present invention relates to a porous electrode, preferably a mesoporous electrode, that can be used in a lithium ion battery. Another object of the present invention relates to a porous electrode, preferably a mesoporous electrode, having a porosity greater than 30% by volume, comprising pores with an average diameter of less than 80 nm, preferably less than 50 nm, a primary particle size of less than 30 nm, preferably a thickness of less than 100 μm, preferably less than 50 μm, more preferably less than 10 μm, characterized in that it does not contain a binder.
[0047] Advantageously, the pores of the porous electrode, preferably the mesoporous electrode, are impregnated with an electrolyte, which is preferably a phase loaded with lithium ions, such as an ionic liquid containing a lithium salt, which may be diluted by an organic solvent or a mixture of organic solvents containing a lithium salt, the lithium salt in the organic solvent being different from the lithium salt dissolved in the ionic liquid, or a solvent diluted in at least one ionic liquid, which preferably accounts for more than 50 weight % of the total lithium ion-loaded phase.
[0048] Advantageously, the pores of the porous, preferably mesoporous electrode are impregnated with a phase loaded with lithium ions, the phase loaded with lithium ions comprising at least 50% by weight of at least one ionic liquid.
[0049] Another object of the present invention relates to a method for manufacturing a battery, which implements the method for manufacturing a porous electrode according to the present invention.
[0050] Another object of the invention relates to a battery comprising at least one porous electrode obtainable by the method of the invention. Another object of the invention relates to a battery in which all electrodes are porous electrodes obtainable by the method of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] 1 and 2 illustrate different aspects of an embodiment of the present invention but do not limit the scope thereof.
[0052] FIG. 1( a ) shows a diffraction pattern and FIG. 1( b ) is a photograph obtained by transmission electron microscopy of primary nanoparticles used for the deposition of an electrode according to the invention by electrophoresis.
[0053] FIG. 2 shows nanoparticles before ( FIG. 2( a ) ) and after ( FIG. 2( b ) ) heat treatment, showing the necking phenomenon.
[0054] Figure 3 A front view in section of a battery comprising an electrode according to the invention is schematically shown, and the structure of the battery comprising an assembly of unit cells covered by a packaging system and terminals is shown.
[0055] Figure 4 A front view showing a detail IV of a porous electrode on a larger scale placed on a substrate serving as current collector.
[0056] List of symbols used in the drawings:
[0057] [Table 1]
[0058] DETAILED DESCRIPTION
[0059] 1. definition
[0060] In the present context, particle size is defined by its largest dimension. "Nanoparticle" refers to any particle or object having nanometer dimensions, at least one dimension of which is less than or equal to 100 nm.
[0061] "Ionic liquid" refers to any liquid salt capable of conducting electricity, which is distinguished from all molten salts by having a melting point of less than 100°C. Some of these salts remain liquid at ambient temperature and do not solidify, even at low temperatures. Such salts are called "ionic liquids at ambient temperature".
[0062] "Mesoporous material" refers to any solid having pores in its structure called "mesopores", wherein the size of the pores is between the size of micropores (width less than 2nm) and the size of macropores (width greater than 50nm), i.e. the size of the pores is 2nm to 50nm. This term corresponds to the terminology adopted by IUPAC (International Union of Pure and Applied Chemistry), which is a reference for those skilled in the art. Therefore, the term "nanopore" is not used herein, although in terms of the definition of nanoparticles, mesopores as defined above have nanometer dimensions, and it is known that those skilled in the art refer to pores whose size is smaller than the size of mesopores as "micropores".
[0063] An introduction to the concept of porosity (and the term disclosed above) is given in the article “Texture of matériaux pulvérulents ou poreux” by F. Rouquerol et al., published in the collection “Techniques de l'Ingénieur” (traité Analyseet Caractérisation, fascicule P 1050); the article also describes techniques for characterizing porosity, in particular the BET method.
[0064] For the purposes of the present invention, "mesoporous electrode" or "mesoporous layer" refers to an electrode or layer having mesopores. As will be explained below, in these electrodes or layers, these mesopores contribute greatly to the total pore volume; the expression "mesoporous electrode or layer having a mesoporous porosity greater than X volume %" used in the description below is used to refer to this state.
[0065] According to the definition of IUPAC, "aggregate" refers to the loosely connected assembly of primary particles. Herein, these primary particles are nanoparticles, and the diameter of the nanoparticles can be determined by transmission electron microscopy. Generally, the aggregates of the primary nanoparticles gathered can be destroyed (that is, reduced to primary nanoparticles) in a suspension of the liquid phase under ultrasound according to techniques known to those skilled in the art.
[0066] According to the IUPAC definition, an "agglomerate" is a tightly connected assembly of primary particles or aggregates.
[0067] According to the present invention, the porous electrode layer, preferably the mesoporous electrode layer, can be deposited by electrophoresis, by dip coating, by ink jetting or by doctor blade, by roller coating, by curtain coating, from a suspension of aggregates or agglomerates of nanoparticles, preferably from a concentrated suspension of agglomerates containing nanoparticles.
[0068] 2. Preparation of nanoparticle suspensions
[0069] In the framework of the present invention, these suspensions of nanoparticles are preferably not prepared from dry nanopowders. These suspensions can be prepared by grinding powders or nanopowders in the liquid phase. In another embodiment of the present invention, the nanoparticles are prepared directly in suspension by precipitation. Synthesizing nanoparticles by precipitation allows very uniformly sized primary nanoparticles with a unimodal size distribution, i.e. very dense and monodisperse nanoparticles with good crystallinity and purity. By using these nanoparticles of very uniform size and narrow distribution, controlled and open porosity can be obtained after deposition. The porous structure obtained after deposition of these nanoparticles has very few closed pores, preferably no closed pores.
[0070] In a more preferred embodiment of the present invention, nanoparticles having their primary size are directly prepared by hydrothermal synthesis or solvothermal synthesis; this technique allows obtaining nanoparticles having a very narrow size distribution, known as "monodisperse nanoparticles". The size of these non-aggregated or non-agglomerated nanopowders / nanoparticles is known as the primary size. Advantageously, the primary size is between 10 nm and 50 nm, preferably between 10 nm and 30 nm; this size is conducive to the formation of an interconnected mesoporous network having electronic conductivity and ionic conductivity due to the necking phenomenon in the subsequent steps of the method.
[0071] The dispersion of monodisperse nanoparticles can be prepared in the presence of a ligand or an organic stabilizer to prevent aggregation or even agglomeration of the nanoparticles.
[0072] The suspension of monodisperse nanoparticles can be purified to remove all potentially interfering ions. Depending on the degree of purification, it can then be subjected to special treatments to form aggregates or agglomerates of controlled size. More precisely, the formation of aggregates or agglomerates is achieved by destabilization of the suspension, wherein the destabilization is brought about in particular by ions, by an increase in the dry extract of the suspension, by a change in the solvent of the suspension, by the addition of destabilizing agents. If the suspension is completely purified, it is stable and ions, usually in the form of salts, are added to destabilize the suspension; these ions are preferably lithium ions (preferably added in the form of LiOH).
[0073] If the suspension is not completely purified, the formation of aggregates or agglomerates will occur spontaneously alone or after aging. This is a simpler way of proceeding because it involves fewer purification steps, but it is more difficult to control the size of the aggregates or agglomerates. One of the important aspects of the manufacture of electrodes according to the present invention is to control the size of the primary particles of the electrode material and the degree of aggregation or agglomeration of the primary particles.
[0074] If the suspension of nanoparticles is stabilized after the formation of the agglomerates, the agglomerates remain in the form of agglomerates; the suspension obtained can be used to prepare mesoporous deposits.
[0075] According to the invention, the suspension of aggregates or agglomerates is used to form a porous electrode layer, preferably a mesoporous electrode layer, by electrophoretic deposition, by inkjet, by doctor blade, by roller coating, by curtain coating or by dip coating.
[0076] According to the applicant's observations, the average diameter of the aggregates or agglomerates of the nanoparticles is 80 nm to 300 nm (preferably 100 nm to 200 nm), and in a subsequent method step a mesoporous layer with an average mesopore diameter of 2 nm to 50 nm is obtained.
[0077] According to the present invention, the porous electrode layer can be electrophoretically deposited from a solution containing aggregates or agglomerates of nanoparticles, preferably from a concentrated liquid suspension containing agglomerates of nanoparticles, by dip coating, by ink jetting, by roller coating, by curtain coating or by a doctor blade, by roller coating, by curtain coating. Advantageously, the porous electrode layer is deposited from a concentrated liquid containing agglomerates of nanoparticles by dip coating.
[0078] The method of depositing aggregates or agglomerates of nanoparticles by electrophoresis, by dip coating, by inkjet, by roller coating, by curtain coating or by doctor blade is simple, safe, easy to implement, easy to industrialize and allows obtaining a uniform final porous layer. Electrophoretic deposition is a technique that allows uniform deposition on large surfaces at high deposition rates. Coating techniques, especially coating techniques by dip coating, roller coating, curtain coating or doctor blade, simplify the management of the bath relative to electrophoretic deposition techniques. Inkjet deposition allows the preparation of localized deposits.
[0079] The porous electrode can be obtained in the form of a thick layer in a single step by roller coating, curtain coating or by doctor blade.
[0080] 3. Properties of the current collector
[0081] In the battery using the porous electrode according to the present invention, the substrate used as the current collector can be a metal substrate, such as a metal foil, or a metallized (i.e., coated with a metal layer) polymer foil or non-metal foil. The substrate is preferably selected from a foil made of titanium, copper, nickel or stainless steel.
[0082] The metal foil may be coated with a layer of a noble metal, in particular chosen from gold, platinum, titanium or an alloy comprising essentially one or more of these metals, or it may have a layer of an ITO type conducting material (which also has the advantage of acting as a diffusion barrier).
[0083] In a battery using a porous electrode according to the present invention, the liquid electrolyte impregnating the porous electrode is in direct contact with the collector. However, when these electrolytes are in contact with a metal substrate and polarized at a high anodic potential for the cathode and a high cathodic potential for the anode, these electrolytes can cause the dissolution of the collector. These side reactions shorten the service life of the battery and accelerate the self-discharge of the battery. To prevent this, in all lithium-ion batteries, an aluminum collector is used at the cathode. Aluminum has the characteristic of undergoing anodic oxidation at very high anodic potentials, and the oxide layer thus formed on the surface of aluminum protects the aluminum from dissolution. However, the melting point of aluminum is close to 600°C, so it cannot be used to manufacture the battery of the present invention. The consolidation treatment of the all-solid-state electrode will lead to the melting of the collector. Therefore, in order to prevent the occurrence of side reactions that shorten the service life of the battery and accelerate the self-discharge of the battery, it is advantageous to use a foil made of titanium as a collector at the cathode. During the operation of the battery, similar to aluminum, the foil made of titanium undergoes anodic oxidation, and its oxide layer prevents any side reactions that dissolve the titanium in contact with the liquid electrolyte. Furthermore, since the melting point of titanium is much higher than that of aluminum, the all-solid-state electrode according to the present invention can be directly manufactured on such a foil.
[0084] By using these solid materials, in particular foils made of titanium, copper or nickel, the cut edges of the battery electrodes can also be protected from corrosion.
[0085] Stainless steel can also be used as current collector, especially when the stainless steel contains titanium or aluminum as alloying elements or when the surface of the stainless steel has a thin layer of protective oxide.
[0086] Other substrates that can be used as current collectors are, for example, semi-noble metals covered with a protective coating, thereby preventing any dissolution of these foils due to the presence of an electrolyte in contact with them.
[0087] These semi-precious metal foils may be foils made of copper, nickel, or foils made of metal alloys, such as foils made of stainless steel, foils made of Fe-Ni alloy, Be-Ni-Cr alloy, Ni-Cr alloy, or Ni-Ti alloy.
[0088] The coating that can be used to protect the substrate used as a current collector can be of different natures. The coating can be:
[0089] • A thin layer obtained by a sol-gel process of the same material as the electrode material. The absence of pores in the film prevents contact between the electrolyte and the metal current collector.
[0090] • Thin layers obtained by vacuum deposition, in particular by physical vapor deposition (PVD) or chemical vapor deposition (CVD), of the same material as the electrode material.
[0091] A dense and defect-free thin metal layer, for example of gold, titanium, platinum, palladium, tungsten or molybdenum. These metals can be used to protect the current collector, since they have good electrical conductivity and can withstand the heat treatment in the subsequent method of manufacturing the electrode. The layer can be produced in particular by electrochemical methods, PVD, CVD, evaporation, ALD.
[0092] - A thin layer of carbon, such as diamond carbon, graphite, deposited by ALD, PVD, CVD, or by inking from a sol-gel solution, which gives, after a heat treatment, an inorganic phase doped with carbon to make it conductive.
[0093] • Conductive oxide layers, such as ITO (Indium Tin Oxide) layers, are deposited only on the cathode substrate, since the oxide is reduced to a low potential.
[0094] ● A conductive nitride layer, such as a TiN layer, deposited only on the cathode substrate, because nitrides will intercalate lithium at low potentials.
[0095] A coating capable of protecting a substrate used as a current collector must be electrically conductive in order to avoid impairing the operation of an electrode subsequently deposited on the coating by giving the electrode an excessively high resistance.
[0096] Usually, in order not to affect the operation of the battery too much, the maximum dissolution current (in μA / cm 2 The surface capacity of the electrode (in μAh / cm 2 indicates) is 1000 times smaller.
[0097] 4. Electrophoretic deposition of layers
[0098] The method according to the present invention advantageously uses the electrophoresis of a suspension of nanoparticles as a deposition technique for a porous electrode layer, preferably a mesoporous electrode layer. The method of depositing an electrode layer by a suspension of nanoparticles is well known (e.g., see patent documentation EP 2 774 194 B1). The substrate can be a metal substrate, such as a metal foil, or a polymer foil or a metallized (i.e., coated with a metal layer) non-metal foil. In a battery using a porous electrode according to the present invention, the substrate used as a current collector is preferably selected from titanium foil, copper foil, stainless steel foil or nickel foil.
[0099] For example, a stainless steel foil with a thickness of 5 μm can be used. The metal foil can be coated with a layer of a noble metal, in particular selected from gold, platinum, titanium or an alloy mainly containing one or more of these metals, or with a layer of an ITO type conductive material (which also has the advantage of acting as a diffusion barrier).
[0100] In a specific embodiment, a layer of electrode material, preferably a thin layer of electrode material, is deposited on the metal layer; the deposit must be very thin (typically tens of nanometers, more typically 10 nm to 100 nm). The deposition can be performed by a sol-gel process. For example, for a porous cathode of LiMn2O4, LiMnO4 can be used.
[0101] Electrophoresis can thus be carried out, a counter electrode is placed in the suspension and a voltage is applied between the conductor substrate and said counter electrode.
[0102] In an advantageous embodiment, the electrophoretic deposition of aggregates or agglomerates of nanoparticles is carried out by pulsed mode constant current electrodeposition; high frequency current pulses are applied, which prevents the formation of bubbles on the electrode surface during deposition and prevents changes in the electric field in the suspension. Advantageously, the thickness of the electrode layer deposited by electrophoresis, preferably by pulsed mode constant current electrodeposition, is less than 10 μm, preferably less than 8 μm, even more preferably from 1 μm to 6 μm.
[0103] 5. Deposition of porous electrode layer by dip coating
[0104] No matter the chemical nature of the nanoparticles used, the aggregates or agglomerates of the nanoparticles can be deposited by dip coating. When the nanoparticles used are less charged or not charged at all, this deposition method is preferred. In order to obtain a layer with a desired thickness, the steps of depositing the aggregates or agglomerates of the nanoparticles by dip coating and the steps of the subsequent drying of the obtained layer are repeated as much as possible as required.
[0105] Although this sequential coating step by dipping / drying is time consuming, the method of deposition by dipping is simple, safe, easy to perform, easy to industrialize, and allows obtaining a uniform and compact final layer.
[0106] 6. Processing and properties of deposited layers
[0107] The deposited layer must be dried; the drying must not initiate the formation of cracks. Drying is therefore preferably carried out under controlled humidity and temperature conditions.
[0108] The dried layer can be consolidated by a pressing and / or heating step (heat treatment). In a very advantageous embodiment of the invention, the treatment leads to partial coalescence of the primary nanoparticles in aggregates or agglomerates and between adjacent aggregates or agglomerates; this phenomenon is called "necking" or "neck formation". It is characterized by partial coalescence of two contacting particles, which remain separated but are connected by a neck (contraction); this is schematically shown in Figure 2. Lithium ions and electrons can migrate within these necks and can diffuse from one particle to another without encountering particle boundaries. The nanoparticles are fused together to ensure that electrons are conducted from one particle to another. As a result, the three-dimensional network composed of interconnected particles has strong ion mobility and electrical conductivity; the network includes pores, preferably mesopores.
[0109] The temperature required to obtain "necking" depends on the material; the duration of the treatment depends on the temperature, taking into account the diffusion nature of the phenomenon causing "necking".
[0110] The heat treatment can also be used to remove organic additives that may be present in the suspension of the nanoparticles used, such as ligands or residual organic stabilizers. When the suspension of the nanoparticles used contains only nanoparticles and a solvent, i.e. when the suspension does not contain ligands or residual organic stabilizers, a heat treatment for consolidation is not necessary.
[0111] Advantageously, the dried, preferably consolidated, electrode layer contains no binder, but may contain up to 10% by weight of carbon, in particular in the form of graphene, carbon black or carbon nanotubes.
[0112] The inventors have observed that, due to the very large specific surface area of the porous, preferably mesoporous, electrode according to the invention, side reactions can occur between the electrode and the electrolyte during its use with a liquid electrolyte; these reactions are at least partially irreversible. In an advantageous embodiment, a very thin dielectric layer (i.e., an electrical insulator) is applied, which covers the porous, preferably mesoporous electrode layer and is defect-free, so as to passivate the electrode surface in order to limit the kinetics of the electrochemical side reactions or even prevent them. Advantageously, the electrical conductivity of the dielectric layer is less than 10 -8 S / cm. Advantageously, the dielectric layer may be a layer of electrically insulating material deposited on and inside the pores of the porous electrode layer, preferably, after step d) of drying the porous electrode layer or after step e) of consolidating the porous electrode layer, the layer of electrically insulating material is deposited chemically in step f) by atomic layer deposition ALD technology or by solution CSD. Advantageously, the deposition is performed at least on one face of the electrode forming the interface between the electrode and the electrolyte. For example, the layer may be made of aluminum oxide Al2O3, silicon oxide SiO2 or zirconium oxide ZrO2. Li4Ti5O12 , or use Li4Ti5O 12 Other materials with similar characteristics do not intercalate lithium ions and behave as electrical insulators at the operating voltage of the cathode.
[0113] Alternatively, the dielectric layer may be an ionic conductor, advantageously with an electrical conductivity of less than 10 -8 S / cm. The material should be selected so as not to intercalate lithium but only transport lithium at the operating voltage of the battery. Advantageously, the dielectric layer may be a layer of ionic conductor material deposited on and inside the pores of the porous electrode layer. Preferably, after step d) of drying the porous electrode layer or after step e) of consolidating the porous electrode layer, the ionic conductor material layer is deposited chemically in step f) by atomic layer deposition ALD technology or by solution CSD. For this purpose, for example, Li3PO4, Li3BO3, lithium lanthanum zirconium oxide (referred to as LLZO) such as Li7La3Zr2O with a wide range of operating potentials may be used. 12 On the other hand, lithium lanthanum titanium oxide (abbreviated as LLTO) such as Li 3x La 2 / 3 – x TiO3, lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP) can only be used in contact with the cathode because these materials have a limited range of working potentials beyond which lithium can be inserted into their crystal structure.
[0114] This deposition further improves the performance of lithium-ion batteries comprising at least one porous electrode according to the invention. The observed improvement consists mainly in the reduction of interfacial Faradaic reactions with the electrolyte. These side reactions are particularly important when the temperature is high; they are the cause of reversible and / or irreversible losses of capacity.
[0115] Very advantageously, the deposition is carried out by a technique capable of performing a blanket coating (also called conformal deposition), i.e. a deposition that faithfully reproduces the atomic morphology of the substrate on which the deposition is performed. Techniques known as ALD (atomic layer deposition) or CSD (chemical solution deposition) are suitable. These techniques can be implemented on the electrode after electrode manufacture, before and / or after the deposition of the separator particles, and before and / or after the assembly of the battery. The deposition technique performed by ALD is performed layer by layer by a cyclic method and can be encapsulated so as to faithfully reproduce the morphology of the substrate; it outlines the entire surface of the electrode. The thickness of the covering coating is generally 1 nm to 5 nm. The deposition technique performed by CSD can be encapsulated so as to faithfully reproduce the morphology of the substrate; it outlines the entire surface of the electrode. The thickness of the covering coating is generally less than 5 nm, preferably 1 nm to 5 nm.
[0116] In this variant of the deposition of the dielectric nanolayer, in order to prevent the dielectric layer from blocking the open pores of the electrode layer, the primary diameter D of the particles of the electrode material is 50 Preferably, it is at least 10 nm.
[0117] The dielectric layer must be deposited only on the porous electrode without any organic binder. In fact, ALD deposition is usually carried out at temperatures between 100°C and 300°C. At this temperature, there is a risk of decomposition of the organic material forming the binder (for example, the polymer contained in the electrode made by tape casting of the ink) and contamination of the ALD reactor. In addition, the presence of residual polymer in contact with the particles of active electrode material prevents the ALD coating from covering the entire surface of the particles, which is detrimental to the effectiveness of ALD.
[0118] For example, an aluminum oxide layer having a thickness of about 1.6 nm is suitable.
[0119] Typically, the method according to the present invention causes the nanoparticles to spontaneously "fuse" together, thereby producing a porous rigid three-dimensional structure without organic binders, wherein the method according to the present invention must utilize an electrophoretic deposition step of nanoparticles of electrode material (active material); such a porous layer, preferably a mesoporous layer, is very suitable for surface treatment by ALD, which is able to penetrate deep into the open pore structure of the layer.
[0120] On the porous, preferably mesoporous electrode, coated with a dielectric layer or not by ALD or by CSD, a porous, preferably mesoporous layer of nanoparticles of a dielectric material can be further deposited, which will serve as a porous separator. The material can be silicon oxide, aluminum oxide, zirconium oxide in particular. This porous layer applied between the electrodes is impregnated with a phase loaded with lithium ions, such as a liquid electrolyte, under capillary action to form a battery cell.
[0121] A solid electrolyte layer can also be deposited as a porous diaphragm, wherein the solid electrolyte can be a lithium ion conductor and an electrical insulator, such as Li3PO4. In one embodiment, a colloidal monodisperse suspension of silicon oxide nanoparticles with a particle size of 20 nm (available directly, for example from Alfa Aesar) is used, which is diluted to 20 g / l. The suspension is then destabilized by adding LiOH to change its ionic charge until aggregates or agglomerates with a size close to 100 nm are obtained. From the colloidal suspension of aggregates or agglomerates of the nanoparticles, two layers each with a thickness of 1.5 μm are formed on the anode and cathode, respectively, by electrophoresis. The two layers are then dried.
[0122] 1. Specific aspects of cathode preparation
[0123] If the electrode according to the present invention is a cathode, the cathode may be made of a cathode material P selected from:
[0124] - Oxides: LiMn2O4; Li 1+x Mn 2-x O4, where 0 < x < 0.15; LiCoO2; LiNiO2; LiMn 1.5 Ni 0.5 O4; LiMn 1.5 Ni 0.5-x X x O4, where X is selected from Al, Fe, Cr, Co, Rh, Nd, other rare earth elements such as Sc, Y, Lu, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and where 0 < x < 0.1; LiMn 2-x M x O4, where M = Er, Dy, Gd, Tb, Yb, Al, Y, Ni, Co, Ti, Sn, As, Mg or a mixture of these compounds, and where 0 < x < 0.4; LiFeO2; LiMn 1 / 3 Ni 1 / 3Co 1 / 3 O2; LiNi 0.8 Co 0.15 Al 0.05 O2; LiAl x Mn 2-x O4, where 0 ≤ x < 0.15; LiNi 1 / x Co 1 / y Mn 1 / z O2, where x + y + z = 10;
[0125] - Phosphates LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3; phosphates of the formula LiMM’PO4, where M and M’ (M ≠ M’) are selected from Fe, Mn, Ni, Co, V;
[0126] - Chalcogenides formed by all lithium: V2O5, V3O8, TiS2,, titanium oxysulfide (TiO y S z , where z = 2 - y and 0.3 ≤ y ≤ 1), tungsten oxysulfide (WO y S z , where 0.6 < y < 3 and 0.1 < z < 2), CuS, CuS2, preferably Li x V2O5, where 0 < x ≤ 2; Li x V3O8, where 0 < x ≤ 1.7; Li xTiS2, where 0 < x ≤ 1; lithium titanium oxysulfide Li x TiO y S z , where z = 2 - y, 0.3 ≤ y ≤ 1; Li x WO y S z ; Li x CuS; Li x CuS2.
[0127] 2. Specific aspects of anode preparation
[0128] If the electrode according to the present invention is an anode, the anode can be made of anode material P, which is selected from:
[0129] - carbon nanotubes, graphene, graphite;
[0130] - lithium iron phosphate (typical molecular formula is LiFePO4);
[0131] - silicon tin oxynitride (typical molecular formula is Si a Sn b O y N z , where a > 0, b > 0, a + b ≤ 2, 0 < y ≤ 4, 0 < z ≤ 3) (also known as SiTON), especially SiSn 0.87 O 1.2 N 1.72 ; and carbon oxynitride, typical molecular formula is Si a Sn b C c O y N z , where a > 0, b > 0, a + b ≤ 2, 0 < c < 10, 0 < y < 24, 0 < z < 17;
[0132] - Si x N y type nitride (especially x = 3 and y = 4); Sn x N y type nitride (especially x = 3 and y = 4); Zn x N y type nitride (especially x = 3 and y = 2); Li 3-x M x N type nitride (where when M = Co, 0 ≤ x ≤ 0.5, when M = Ni, 0 ≤ x ≤ 0.6, when M = Cu, 0 ≤ x ≤ 0.3); Si 3-x M x N4 type nitride, where M = Co or Fe, and 0 ≤ x ≤ 3;
[0133] -Oxides SnO2, SnO, Li2SnO3, SnSiO3, Li x SiO y (x>=0 and 2>y>0), Li4Ti5O 12 、TiNb2O7、Co3O4、SnB 0.6 P 0.4 O 2.9 and TiO2,
[0134] - a complex oxide TiNb2O7 comprising 0 to 10% by weight of carbon, the carbon preferably being selected from graphene and carbon nanotubes.
[0135] 3. Fabrication of a battery using the electrode according to the invention
[0136] The porous electrode according to the invention can be covered with a dielectric layer by ALD or by CSD or can be uncovered with a dielectric layer.
[0137] Subsequently, the electrodes, covered or uncovered, may be covered with a porous layer acting as a diaphragm, so that there is a porous layer between the electrodes covered with a dielectric layer or uncovered by ALD or by CSD. In one embodiment, the material used to make this porous layer acting as a diaphragm is selected from inorganic materials with a low melting point, which are electrical insulators and are in stable contact with the electrodes during the hot pressing step. The more refractory the material, the more it needs to be heated at high temperatures, thus risking a change in the interface with the electrode material, especially under the effect of mutual diffusion, which can produce side reactions and form a depletion layer, wherein the electrochemical properties of the depletion layer are different from those of the same material deeper from the interface.
[0138] The material used to make the porous layer that acts as a diaphragm is preferably an inorganic material. In a specific embodiment, the material used to make the porous layer that acts as a diaphragm is an electrical insulating material. Preferably, it can be selected from Al2O3, SiO2, ZrO2.
[0139] Alternatively, the material used to make the porous layer that functions as a separator may be an ion conductor material, such as a solid electrolyte.
[0140] According to the invention, the solid electrolyte material used to produce the porous layer acting as a separator may be selected in particular from:
[0141] ○With formula Li d A 1 x A 2 y (TO4) z of garnet, among which
[0142] ■A 1represents a cation in the +II oxidation state, preferably Ca, Mg, Sr, Ba, Fe, Mn, Zn, Y, Gd; and wherein
[0143] ■A 2 represents a cation in the +III oxidation state, preferably Al, Fe, Cr, Ga, Ti, La; and wherein
[0144] ■ (TO4) represents an anion in which T is an atom in the +IV oxidation state, which is located at the center of the tetrahedron formed by the oxygen atoms, and in which TO4 advantageously represents a silicate or zirconate anion, it being known that all or part of the element T in the +IV oxidation state may be replaced by atoms in the +III or +V oxidation state, such as Al, Fe, As, V, Nb, In, Ta;
[0145] ■ It is known that: d is 2 to 10, preferably 3 to 9, even more preferably 4 to 8; x is 2.6 to 3.4 (preferably 2.8 to 3.2); y is 1.7 to 2.3 (preferably 1.9 to 2.1), and z is 2.9 to 3.1;
[0146] ○ Garnet, preferably selected from: Li7La3Zr2O 12 ;Li6La2BaTa2O 12 ;Li 5.5 LqCy 1.75 In 0.25 O 12 ;Li5La3M2O 12 , where M = Nb or Ta or a mixture of these two compounds; Li 7-x Ba x La 3-x M2O 12 , where 0≤x≤1, and M=Nb or Ta or a mixture of these two compounds; Li 7-x Ln3Z 2-x M x O 12 , wherein 0≤x≤2, and M=Al, Ga or Ta or a mixture of two or three of these compounds;
[0147] ○ Lithium phosphate, preferably selected from: NaSICON type lithium phosphate, Li3PO4; LiPO3; Li3Al 0.4 Sc 1.6 (PO4)3, which is called "LASP"; Li 1.2 Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P 1-x Si xO4)3, of which 1.8 <x<2.3;Li 1+6x Zr2(P 1-x B x O4)3, where 0≤x≤0.25; Li3(Sc 2-x M x )(PO4)3, where M = Al or Y, and 0≤x≤1; Li 1+x M x (Sc) 2-x (PO4)3, where M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3, wherein 0≤x≤0.8, 0≤y≤1, and M=Al or Y or a mixture of these two compounds; Li 1+x M x (Ga) 2-x (PO4)3, wherein M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1, is called "LATP"; or Li 1+x Al x Ge 2-x (PO4)3, where 0≤x≤1; or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12 , wherein 0≤x≤0.8, 0≤y≤1.0 and 0≤z≤0.6, and M=Al, Ga or Y or a mixture of two or three of these compounds; Li 3+y (Sc 2-x M x )Q y P 3-y O 12 , wherein M=Al and / or Y and Q=Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y M x Sc 2-x Q y P 3-y O 12, wherein M = Al, Y, Ga or a mixture of these three compounds, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y+z M x (Ga 1- y Sc y ) 2-x Q z P 3-z O 12 , wherein 0≤x≤0.8; 0≤y≤1; 0≤z≤0.6, wherein M=Al or Y or a mixture of these two compounds, and Q=Si and / or Se; or Li 1+x Zr 2-x B x (PO4)3, where 0≤x≤0.25; or Li 1+x Zr 2-x Ca x (PO4)3, where 0≤x≤0.25; or Li 1+x M 3 x M 2-x P3O 12 , where 0≤x≤1, and M 3 =Cr, V, Ca, B, Mg, Bi and / or Mo, M =Sc, Sn, Zr, Hf, Se or Si or a mixture of these compounds;
[0148] ○ Lithium borate, preferably selected from: Li3(Sc 2-x M x )(BO3)3, where M = Al or Y, and 0≤x≤1; Li 1+x M x (Sc) 2-x (BO3)3, wherein M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1- y Sc y ) 2-x (BO3)3, where 0≤x≤0.8, 0≤y≤1, and M=Al or Y; Li 1+x M x (Ga) 2-x (BO3)3, wherein M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li3BO3, Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4;
[0149] ○ Nitrogen oxides, preferably selected from Li3PO 4-x N 2x / 3 、Li4SiO 4-x N 2x / 3 、Li4GeO 4-x N 2x / 3 , where 0 < x < 4, or Li3BO 3-x N 2x / 3 , where 0 < x < 3;
[0150] ○ Lithium compounds based on lithium phosphorus nitrogen oxides (referred to as "LiPON"), which are in the form of Li x PO y N z where x ~ 2.8, 2y + 3z ~ 7.8 and 0.16 ≤ z ≤ 0.4, especially Li 2.9 PO 3.3 N 0.46 , or can also be the compound Li w PO x N y S z in the form of, where 2x + 3y + 2z = 5 = w, or is the compound Li w PO x N y S z , where 3.2 ≤ x ≤ 3.8, 0.13 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.2, 2.9 ≤ w ≤ 3.3, or is Li t P x Al y O u N v S w in the form of a compound, where 5x + 3y = 5, 2u + 3v + 2w = 5 + t, 2.9 ≤ t ≤ 3.3, 0.84 ≤ x ≤ 0.94,, 0.094 ≤ y ≤ 0.26, 3.2 ≤ u ≤ 3.8, 0.13 ≤ v ≤ 0.46, 0 ≤ w ≤ 0.2;
[0151] ○ Nitrogen oxides based on lithium phosphorus or lithium boron, which are respectively referred to as "LiPON" and "LIBON", and can also contain silicon, sulfur, zirconium, aluminum, or a combination of aluminum, boron, sulfur, and / or silicon, and for materials based on lithium phosphorus nitrogen oxides, boron can be included;
[0152] ○ Lithium compounds based on lithium, phosphorus, and silicon nitrogen oxides, called "LiSiPON", especially Li 1.9 Si 0.28 P 1.0 O 1.1 N 1.0 ;
[0153] ○ Lithium oxynitrides of the LiBON, LiBSO, LiSiPON, LiSON, thio-LiSiCON, LiPONB type (where B, P, and S represent boron, phosphorus, and sulfur, respectively);
[0154] ○ Lithium oxynitrides of the LiBSO type, such as (1-x)LiBO2 - xLi2SO4, where 0.4 ≤ x ≤ 0.8;
[0155] ○ Lithium oxides, preferably selected from Li7La3Zr2O 12 or Li 5+x La3(Zr x ,A 2-x )O 12 , where A = Sc, Y, Al, Ga and 1.4 ≤ x ≤ 2, or Li 0.35 La 0.55 TiO3 or Li 3x La 2 / 3-x TiO3, where 0 ≤ x ≤ 0.16 (LLTO);
[0156] ○ Silicates, preferably selected from Li2Si2O5, Li2SiO3, Li2Si2O6, LiAlSiO4, Li4SiO4, LiAlSi2O6;
[0157] ○ Perovskite - type solid electrolytes, selected from: Li3OA, where A is a halogen element or a mixed halogen element, preferably at least one element selected from F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, preferably at least one element selected from Mg, Ca, Ba, Sr, or a mixture of two, three, or four of these elements, and A is a halogen element or a mixed halogen element, preferably at least one element selected from F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M 3 x / 3OA, where 0 ≤ x ≤ 3, M 3 is a trivalent metal, and A is a halogen element or a mixed halogen element, preferably at least one element selected from F, Cl, Br, I, or a mixture of two, three, or four of these elements; or LiCOX z Y (1-z) ,, where X and Y are halogen elements as listed for A above, and 0 ≤ z ≤ 1;
[0158] ○ The compound La 0.51 Li 0.34 Ti2.94 , Li 3.4 V 0.4 Ge 0.6 O4, Li2O-Nb2O5, LiAlGaSPO4;
[0159] ○Based on Li2CO3, B2O3, Li2O, Al(PO3)3LiF, P2S3, Li2S, Li3N, Li 14 Zn(GeO4)4、Li 3.6 Ge 0.6 V 0.4 O4, LiTi2(PO4)3, Li 3.25 Ge 0.25 P 0.25 S4, Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1+x Al x M 2-x (PO4)3 (wherein M = Ge, Ti and / or Hf, and where 0 <x<1)、Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (wherein 0≤x≤1 and 0≤y≤1).
[0160] Advantageously, the porous layer acting as a separator can be deposited from a suspension of nanoparticles in the same way as the electrode layer and with the support of the electrode layer, by electrophoresis, by dip coating, by inkjet or by doctor blade, by roller coating, by curtain coating.
[0161] It is preferred that the electrode according to the present invention is covered with a porous layer functioning as a separator and then the electrodes are stacked in such a manner that the porous layers are in contact.
[0162] This stack, which comprises cathodes and anodes alternating in sequence, preferably in the form of thin layers covered with a porous layer, is then subjected to vacuum hot pressing, it being understood that at least one cathode according to the invention or at least one anode according to the invention is used in the stack. The pressure and temperature used during the hot pressing of the stack which enables the assembly to be obtained depend in particular on the nature of the materials constituting the stack and on the size of the primary particles used to make the electrodes and the porous layer acting as a separator.
[0163] Advantageously, the stack is placed under a pressure of 0.5 MPa to 3 MPa, preferably about 1.5 MPa, and then vacuum dried. This allows the stack to be maintained during drying. The platens of the press are then heated to a set temperature, preferably 450° C., at a rate of several degrees C. per second. At 450° C., the stack is then hot pressed at a pressure capable of assembling the stack, preferably at 45 MPa for 1 minute, and the system is then cooled to ambient temperature.
[0164] After assembly, a rigid multilayer system is obtained, formed of one or more assembled unit cells.
[0165] In an advantageous embodiment, a very thin dielectric layer (i.e., an electrical insulator), preferably free of defects, is applied and covered on the hot pressed stack. This enables the entire surface of the anode 12, cathode 22 and / or porous layer 13, 23 acting as a diaphragm to be covered with a very thin dielectric layer (i.e., an electrical insulator), preferably free of defects, in a single treatment. In addition to passivating the electrode surfaces, the treatment can also cover only the accessible surfaces of the mesoporous structure, i.e., the surfaces of the layers that will be in contact with the electrolyte.
[0166] This deposition improves the performance of lithium-ion batteries comprising at least one porous electrode according to the invention. The observed improvement is mainly a reduction of the Faradaic reactions at the interface between the electrolyte and the electrode.
[0167] Very advantageously, the deposition is carried out by a technique capable of blanket coating (also called conformal deposition), i.e. a deposition that faithfully reproduces the atomic topography of the substrate on which the deposition is carried out. The techniques known as ALD (atomic layer deposition) or CSD (chemical solution deposition) are suitable. These deposition techniques by ALD and by CSD make it possible to obtain a coating that outlines the entire surface of the electrode. The thickness of the blanket coating is generally less than 5 nm, preferably between 1 nm and 5 nm.
[0168] For a battery comprising an electrode according to the invention, its all-solid-state structure, which does not contain organic materials, is able to withstand high temperatures and is compatible with deposition methods by ALD.
[0169] The dielectric layer applied to the hot pressed stack to protect and passivate the accessible surface of the stack can be, for example, silicon oxide, zirconium oxide, aluminum oxide Al2O3. The dielectric layer can also be an ionic conductor, advantageously with an electrical conductivity of less than 10 -8 S / cm. The material should be selected so as not to intercalate lithium but only transport lithium at the operating voltage of the battery. For this purpose, for example, Li3PO4, Li3BO3, lithium lanthanum zirconium oxide (referred to as LLZO) such as Li7La3Zr2O, which have a wide range of operating potentials, can be used. 12 .
[0170] However, if Figure 4 As shown, the dielectric layers 62, 63 applied by ALD or CSD to the hot pressed stack only cover the surface of the porous deposit and a portion of the surface of the current collector.
[0171] A dielectric layer less than 5 nm thick applied by ALD or CSD to the hot pressed stack does not prevent the passage of electrons. Since the electrodes are partially sintered, the electrons pass through the welded portions (necked portions) between the electrode material particles. The "welded" region 60 between the mesoporous deposit and the substrate is not covered by the dielectric layer.
[0172] The dielectric layer applied by ALD or CSD covers only the free surfaces of the holes 61 , in particular the accessible surfaces of the electrodes 22 and the substrate 21 .
[0173] The material used to make the dielectric layer is particularly effective in blocking electrochemical dissolution reactions. Furthermore, the insulating deposit produced by ALD or CSD is particularly effective when it assumes the role of corrosion protection. The insulating deposit is certainly of a thin thickness, but has complete coverage and is free of defects.
[0174] The dielectric layer may be formed from a stack of thin films, thereby forming a multi-layer structure. These thin films may have different chemical properties, thereby forming a multi-layer and multi-material structure. In addition, when the dielectric layer is formed from a stack of thin films, preferably a stack of thin films forming a multi-layer and multi-material structure, the dielectric layer needle has a better corrosion resistance. For example, a dielectric layer including a 2nm Al2O3 film and a 2nm ZrO2 film is more effective than a dielectric layer including a single layer of 4nm Al2O3 film.
[0175] Regardless of whether the dielectric layer is thick and / or has a multi-layer structure, it can effectively protect the substrate from corrosion caused by the use of liquid electrolytes without affecting the passage of electrons.
[0176] At the interface, only lithium ions must pass, but not electrons. An ion-conducting insulator such as Li3PO4 can be used as a dielectric layer with a greater thickness, preferably 1 nm to 5 nm, without affecting the operation of the battery. A dielectric layer having a multilayer structure can also be deposited by ALD or by CSD, the dielectric layer comprising: a first layer deposited on the hot-pressed stack, the first layer consisting of an ion-conducting insulator material such as a solid electrolyte, the first layer preferably having a thickness of 1 nm to 5 nm; and a second layer deposited on the first layer, the second layer comprising an ion and electronic insulator material, and the second layer having a very thin thickness, ideally less than 1 nm, so that the resistance of the battery is not too large.
[0177] This assembly, covered or not covered with a dielectric layer, can then be impregnated with a phase loaded with lithium ions, preferably in an electrolyte.
[0178] 4. Impregnation of assembled batteries, more specifically of electrode layers and battery separators
[0179] After the stack is assembled by hot pressing to form a battery, it can be impregnated with a phase loaded with lithium ions. This phase can be a solution formed by dissolving a lithium salt in an organic solvent or a mixture of organic solvents, and / or in a polymer comprising at least one lithium salt, and / or in an ionic liquid (i.e., molten lithium salt) comprising at least one lithium salt. This phase can also be a solution formed by a mixture of these components. The inventors have found that the porous electrode according to the present invention is able to adsorb the liquid phase by simple capillary action. This completely unexpected effect is peculiar to the deposit of the porous electrode, preferably the mesoporous electrode, according to the present invention; when the average diameter D of the pores 50 This effect is particularly advantageous when the component is 2 nm to 80 nm, preferably 2 nm to 50 nm, preferably 6 nm to 30 nm, preferably 8 nm to 20 nm. Preferably, when the component is made of a ceramic material, the pores of the component are easily wetted by an ionic liquid, a mixture of ionic liquids, or a solution containing at least 50% by weight of at least one ionic liquid diluted with an organic solvent or a mixture of organic solvents. The pores of the component are impregnated with a phase loaded with lithium ions, i.e., with an electrolyte, such as an ionic liquid containing a lithium salt, which can be diluted with an organic solvent or a mixture of organic solvents, wherein the organic solvent or the mixture of organic solvents contains a lithium salt that can be different from the lithium salt dissolved in the ionic liquid.
[0180] The impregnation can be done on the anode or the cathode, or on both.
[0181] In an advantageous embodiment of the invention, the porous electrode, preferably the mesoporous electrode, has a porosity greater than 30% by volume and an average pore diameter D 50 The primary diameter of the particles is less than 80 nm, preferably less than 50 nm, and less than 30 nm. Advantageously, the thickness is less than 100 μm, less than 50 μm, less than 10 μm, and preferably 2.5 μm to 4.5 μm, thereby reducing the final thickness of the battery. The electrode does not contain a binder.
[0182] Advantageously, the porous electrode, preferably in the form of a thin layer, has a porosity of 35% to 50% by volume, more preferably 40% to 50% by volume; it is preferably a mesoporous electrode.
[0183] In an advantageous embodiment of the invention, the porosity of the porous layer acting as a separator is greater than 30% by volume, and the average diameter D of the pores is 50The average diameter of the mesopores is less than 50 nm. The porous layer, which acts as a separator, can adsorb liquid phases, such as phases loaded with lithium ions, in its pores by simple capillary action. 50 This effect is particularly advantageous when the thickness is 2 nm to 50 nm, preferably 6 nm to 30 nm, preferably 8 nm to 20 nm. Advantageously, its thickness is less than 10 μm. It contains no binder. Advantageously, the porosity of the porous layer acting as a separator is 35% to 50% by volume, more preferably 40% to 50% by volume; it is preferably a mesoporous layer.
[0184] The "nano-confined" or "nano-trapped" liquid in the pores, preferably mesopores, can no longer leave. This is linked to a phenomenon referred to herein as "adsorption in mesoporous structures" (which does not seem to have been described in the literature on lithium-ion batteries), and the liquid can no longer leave even when the battery is placed in a vacuum. The battery is then considered a quasi-solid-state battery.
[0185] The phase carrying lithium ions may be an ionic liquid containing a lithium salt, which may be diluted with an organic solvent or a mixture of organic solvents containing a lithium salt which may be different from the lithium salt dissolved in the ionic liquid.
[0186] Ionic liquids are formed by the association of cations and anions; the cations and anions are selected in such a way that the ionic liquid is in a liquid state within the operating temperature range of the battery. Ionic liquids have the following advantages: high thermal stability, low flammability, non-volatility, low toxicity, and good wettability to ceramics, where ceramics are materials that can be used as electrode materials. Surprisingly, the proportion of ionic liquid contained in the phase carrying lithium ions can be greater than 50%, preferably greater than 60%, and even more preferably greater than 70%, which is different from lithium ion batteries in the prior art, in which the weight percentage of ionic liquid in the electrolyte must be less than 50% by weight so that the battery maintains a high capacity and voltage during discharge and maintains good stability during cycling. As shown in patent application US 2010 / 209 783A1, when the weight percentage of ionic liquid exceeds 50% by weight, the capacity of the battery in the prior art decreases. This phenomenon can be explained by the presence of polymer binders in the electrolyte of prior art batteries; these binders are slightly wetted by the ionic liquid, resulting in poor ionic conduction in the phase carrying lithium ions, leading to reduced battery capacity.
[0187] Preferably, the cells using the porous electrode according to the invention are binder-free. Thus, these cells can use a lithium-ion-loaded phase comprising more than 50% by weight of at least one ionic liquid without reducing the ultimate capacity of the cell.
[0188] The phase carrying lithium ions may comprise a mixture of several ionic liquids.
[0189] Advantageously, the ionic liquid may be 1-ethyl-3-methylimidazolium (also known as EMI + ) and / or N-propyl-N-methylpyrrolidinium (also known as PYR 13 + ) and / or N-butyl-N-methylpyrrolidinium (also known as PYR 14 + ) type cations and bis(trifluoromethylsulfonyl)imide (TFSI - ) and / or bis(fluorosulfonyl)imide (FSI - ) type of anion association. To form an electrolyte, a lithium salt such as LiTFSI can be dissolved in an ionic liquid used as a solvent, or in a solvent such as γ-butyrolactone. γ-Butyrolactone can prevent the crystallization of the ionic liquid, especially the crystallization of the ionic liquid at low temperatures, where the crystallization of the ionic liquid leads to a higher operating temperature range.
[0190] The phase loaded with lithium ions may be an electrolyte solution comprising PYR14TFSI and LiTFSI; these abbreviations are defined below.
[0191] Advantageously, when the porous anode or cathode comprises lithium phosphate, the phase carrying lithium ions comprises a solid electrolyte, such as LiBH4, or a mixture of LiBH4 and one or more compounds selected from LiCl, LiI and LiBr. LiBH4 is a good conductor of lithium and has a low melting point, which facilitates its impregnation in the porous electrode, especially by immersion. Due to its extremely high reducibility, LiBH4 is rarely used as an electrolyte. By using a protective film on the surface of the porous lithium phosphate electrode, the reduction of the electrode material, especially the cathode material, by LiBH4 is prevented, thereby preventing the degradation of the electrode.
[0192] Advantageously, the phase loaded with lithium ions comprises at least one ionic liquid, preferably at least one room temperature ionic liquid, such as PYR14TFSI, which is dilutable in at least one solvent, such as gamma-butyrolactone.
[0193] Advantageously, the phase loaded with lithium ions comprises from 10% to 40% by weight of solvent, preferably from 30% to 40% by weight of solvent, even more preferably from 30% to 40% by weight of gamma-butyrolactone.
[0194] Advantageously, the phase loaded with lithium ions comprises more than 50% by weight of at least one ionic liquid and less than 50% by weight of solvent, which reduces the safety risk and the risk of fire in the event of a malfunction of a battery comprising such a phase loaded with lithium ions.
[0195] Advantageously, the lithium ion-carrying phase comprises:
[0196] - 30 to 40% by weight of a solvent, preferably 30 to 40% by weight of gamma-butyrolactone, and
[0197] - more than 50% by weight of at least one ionic liquid, preferably more than 50% by weight of PYR14TFSI.
[0198] The phase loaded with lithium ions may be an electrolyte comprising PYR14TFSI, LiTFSI and γ-butyrolactone, preferably an electrolyte comprising about 90 wt % of PYR14TFSI, 0.7 M of LiTFSI, and 10 wt % of γ-butyrolactone.
[0199] After impregnation with the liquid phase loaded with lithium ions, the assembly is dried, preferably by means of a N2 curtain, so as to obtain a lithium-ion battery comprising at least one, preferably several, electrochemical cells, each of which comprises an electrode according to the invention.
[0200] Now we will describe the Li3Al 0.4 Sc 1.6 (PO4)3, with a solid electrolyte-based separator. 0.4 Sc 1.6 The mesoporous cathode layer (LiMn2O4) of the mesoporous layer of (PO4)3 and the mesoporous cathode layer (LiMn2O4) of the mesoporous layer of (PO4)3 are also coated with Li3Al 0.4 Sc 1.6 The mesoporous anode layer of the (PO4)3 mesoporous layer (Li4Ti5O 12 ).
[0201] A suspension of nanoparticles of the electrolyte material is prepared hydrothermally, which directly yields nanoparticles with good crystallinity. The electrolyte layer can be deposited on the cathode layer and / or anode layer by electrophoresis, by inkjet, by doctor blade, by roller coating, by curtain coating or by dip coating, whether or not the cathode layer and / or anode layer is previously coated with a dielectric layer deposited by ALD. The assembly is performed by hot pressing in an inert atmosphere at a temperature of 300° C. to 500° C., preferably 350° C. to 450° C., and a pressure of 50 MPa to 100 MPa, for example at 350° C. and 100 MPa.
[0202] The unit cell, which does not contain any organic material and is completely solid and rigid, is then immersed in a lithium-ion conductive liquid electrolyte by immersion. Due to the open pores and the small size of the pores (less than 50 nm), the immersion of the entire unit cell (electrodes and the mesoporous Li3Al0.4 Sc 1.6 (PO4)3). For example, the liquid electrolyte may be LiPF6 or LiBF4 dissolved in an aprotic solvent, or an ionic liquid containing a lithium salt. The ionic liquid and the organic electrolyte may also be mixed. For example, 50 wt % of LiPF6 dissolved in EC / DMC may be mixed with an ionic liquid containing a lithium salt of the type LiTFSI:PYR14TFSI in a molar ratio of 1:9. A mixture of ionic liquids capable of operating at low temperatures may also be prepared, such as a mixture of LiTFSI:PYR13FSI:PYR14TFSI (molar ratio of 2:9:9).
[0203] EC is a common abbreviation for ethylene carbonate (CAS no.: 96-49-1). DMC is a common abbreviation for dimethyl carbonate (CAS no.: 616-38-6). LITFSI is a common abbreviation for lithium bis(trifluoromethanesulfonyl)imide (CAS no.: 90076-65-6). PYR13FSI is a common abbreviation for N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide. PYR14TFSI is a common abbreviation for 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide.
[0204] Here we describe another example of manufacturing a lithium-ion battery according to the present invention. The method comprises the following steps:
[0205] (1) providing a colloidal suspension comprising aggregates or agglomerates of nanoparticles of at least one cathode material, wherein the average primary diameter D of the nanoparticles of the cathode material is 50 Less than or equal to 50nm;
[0206] (2) providing a colloidal suspension comprising aggregates or agglomerates of nanoparticles of at least one anode material, wherein the average primary diameter D of the nanoparticles of the anode material is 50 Less than or equal to 50nm.
[0207] (3) providing two flat conductive substrates, preferably metal substrates, which can be used as current collectors for the battery,
[0208] (4) depositing at least one cathode layer or an anode layer on the substrate provided in step (3) from a suspension of nanoparticles of the material provided in step (1) or step (2) by dip coating, by ink jetting, by doctor blade, by roller coating, by curtain coating or by electrophoresis, preferably by pulsed current constant current electrodeposition,
[0209] (5) drying the layer obtained in step (4),
[0210] (6) Optionally, depositing an electrically insulating material layer on or inside the holes of the cathode layer and / or anode layer in step (5) by ALD.
[0211] (7) Preferably, the average primary diameter D is prepared by electrophoresis, by dip coating, by ink jetting, by doctor blade, by roller coating or by curtain coating. 50 Less than or equal to 50nm or average diameter D 50 A colloidal suspension of nanoparticles of the aggregated material or agglomerated material having a size of about 100 nm is deposited on the cathode layer or anode layer obtained in step (5) and / or step (6) with a film of an electrically insulating material or an ion conductive material or an electrically insulating material capable of ion conduction, preferably a porous film, preferably a mesoporous film,
[0212] (8) drying the layer obtained in step (7),
[0213] (9) realizing a stack comprising alternating cathode layers and anode layers, wherein the cathode layers and the anode layers are preferably offset in the transverse direction,
[0214] (10) hot pressing the anode layer and cathode layer obtained in step (9) so as to be juxtaposed with the membrane present on the anode layer and cathode layer obtained in step (8) and obtaining an assembled stack,
[0215] (11) Optionally, depositing a layer of electrically insulating material by ALD on the hot-pressed stack obtained in step (10),
[0216] (12) Impregnating the structure obtained in step (10) with a phase carrying lithium ions to obtain an impregnated structure, preferably a unit cell.
[0217] The order of steps (1), (2) and (3) is not important.
[0218] A lithium-ion unit cell with a very high power density is thereby obtained. As shown above, the "nano-confined" or "nano-trapped" liquid in the mesopores can no longer leave; the battery is then considered a quasi-solid-state battery.
[0219] Compared with depositing the electrically insulating material layer in step (6), it is preferred to deposit the electrically insulating material layer on the hot-pressed stack (i.e., the heat-assembled stack) obtained in step (10) by ALD; compared with depositing the electrically insulating material layer on each electrode separately, depositing the electrically insulating material layer on the hot-pressed stack by ALD is simpler.
[0220] We describe here the manufacture of lithium-ion batteries suitable for low temperatures. As shown above, when the temperature decreases, the series resistance of the battery increases. For all-solid-state lithium-ion batteries (for example, such as those described in patent applications WO 2013 / 064 781 or WO 2013 / 064 779), the ionic conductivity of the electrolyte decreases by about half when the temperature drops by 7°C. To solve this problem, a battery according to the invention is used, which has a mesoporous electrode and a porous layer that acts as a separator, the porous layer is preferably a mesoporous layer, and the porous layer is impregnated with an electrolyte, which is preferably an ionic liquid containing lithium ions; the ionic liquid can be diluted by adding a suitable organic solvent. For example, a mixture of 50% by weight of LiPF6 dissolved in EC / DMC and LiTFSI:PYR14TFSI in a molar ratio of 1:9 can be used, or an electrolyte containing 90% by weight of PYR14TFSI and 0.7M of LiTFSI, and 10% by weight of γ-butyrolactone can be used. As described above, after step (11), impregnation is performed after the stack comprising alternating cathode and anode layers is assembled, wherein the cathode and anode layers are covered with a porous layer that functions as a separator.
[0221] For example, the average diameter D 50 The electrode is deposited by aggregated nanoparticles or agglomerated nanoparticles having an average diameter D of about 100 nm. 50 Primary nanoparticles of 50 nm or less are obtained, wherein the deposition of the electrode is deposition of the cathode or deposition of the anode, or preferably deposition of both the cathode and the anode; the thickness of each electrode may be about 4 μm.
[0222] The method according to the present invention can be used to manufacture porous electrodes or mesoporous electrodes in electronic, electrical or electrotechnical devices, preferably, to manufacture porous electrodes or mesoporous electrodes in devices selected from the group consisting of batteries, capacitors, supercapacitors, capacitors, resistors, inductors, transistors, and photovoltaic cells, wherein the porous electrode or mesoporous electrode is especially a thin layer or a thicker layer with a thickness of about 50μm or 100μm.
[0223] 5. Encapsulation
[0224] The battery or assembly, covered or not covered with a dielectric layer, must then be encapsulated by an appropriate method to ensure protection of the battery or assembly from the atmosphere, wherein the battery or assembly is a multilayer rigid system formed by one or more assembled unit cells and may be impregnated with a phase loaded with lithium ions. The encapsulation system 30 comprises at least one layer, and preferably a stack of several layers. If the encapsulation system 30 consists of a single layer, it must be deposited by ALD or made of parylene and / or polyimide. These encapsulation layers must be chemically stable, resistant to high temperatures and impermeable to the atmosphere (barrier layer). One of the methods described in patent applications WO 2017 / 115032, WO 2016 / 001584, WO2016 / 001588 or WO 2014 / 131997 can be used. Preferably, the at least one encapsulation layer covers four of the six faces of the battery, the remaining two faces of the battery being covered by terminals.
[0225] Advantageously, the cell or assembly can be covered with a packaging system 30 formed by a stack of several layers, ie a sequence, preferably a z-sequence, comprising:
[0226] - a first coating layer deposited on the stack of anode foil and cathode foil, the first coating layer preferably being selected from Parylene, Parylene F-type, polyimide, epoxy resin, silicone resin, polyamide and / or mixtures thereof,
[0227] - a second coating layer deposited on said first coating layer by atomic layer deposition, said second coating layer comprising an electrically insulating material.
[0228] The sequence can be repeated z times, z ≥ 1. The multilayer sequence has a barrier effect. The more times the sequence of the encapsulation system is repeated, the greater the barrier effect. When a large number of thin layers are deposited, the barrier effect is very significant.
[0229] Advantageously, the first coating is a polymer layer, for example made of silicone (e.g. deposited from hexamethyldisiloxane (HMDSO) by dipping or by plasma-assisted chemical vapor deposition), or epoxy, or polyimide, polyamide, or Parylene (more commonly known as Parylene), preferably based on polyimide and / or Parylene. The first coating protects the sensitive components of the battery from its environment. The thickness of the first coating is preferably 0.5 μm to 3 μm.
[0230] Advantageously, the first coating may be Parylene type C, Parylene type D, Parylene type N (CAS 1633-22-3), Parylene type F or a mixture of Parylene type C, D, N and / or F. Parylene (also known as poly(p-xylene) or poly(p-xylene)) is a transparent semi-crystalline dielectric material having high thermodynamic stability, excellent solvent resistance and very low permeability. Parylene also has barrier properties, making it possible to protect the battery from its external environment. When the first coating is made of Parylene type F, the protection of the battery is increased. Vacuum deposition can be performed by chemical vapor deposition (CVD). Advantageously, the first encapsulation layer is obtained by polycondensation of gaseous monomers deposited on the surface by chemical vapor deposition (CVD), so that a thin and uniform conformal coating of the entire accessible surface of the stack can be obtained. The first coating can accompany the volume changes of the battery during operation of the battery and facilitate specific cutting of the battery by the elasticity of the first coating. The thickness of the first encapsulation layer is 2 μm to 10 μm, preferably 2 μm to 5 μm, and even more preferably about 3 μm. All accessible surfaces of the stack can be covered, access to the pores of these accessible surfaces can be closed only on the surface, and the chemical properties of the substrate can be made uniform. Since the size of the deposited polymer is too large to enter the pores of the stack, the first coating will not enter the pores of the cell or component.
[0231] Advantageously, the first coating is rigid; it cannot be considered as a flexible surface. Encapsulation can therefore be carried out directly on the stack, the coating being able to penetrate into all accessible cavities. It should be noted here that, since no binder is present in the pores of the electrodes and / or electrolyte according to the invention, the battery can be vacuum processed.
[0232] In one embodiment, a first layer made of Parylene is deposited, such as a C-type Parylene layer, a D-type Parylene layer, an N-type Parylene (CAS 1633-22-3) layer, or a layer comprising a mixture of C-type, D-type and / or N-type Parylene. Parylene (also known as poly(p-xylene) or poly(p-xylene)) is a transparent, semi-crystalline dielectric material with high thermodynamic stability, excellent solvent resistance, and very low permeability.
[0233] The Parylene layer can also protect the sensitive components of the battery from its environment. When the first encapsulation layer is made of N-type Parylene, the protection of the battery is increased. However, the inventors have observed that when the first layer is based on Parylene, it does not have sufficient stability in the presence of oxygen. When the first layer is based on polyimide, it does not have sufficient sealing, especially in the presence of water. Therefore, a second layer is deposited covering the first layer.
[0234] Advantageously, a second coating layer comprising an electrically insulating material, preferably an inorganic material, can be deposited on this first layer by a conformal deposition technique, such as atomic layer deposition (ALD). Thus, a conformal coating is obtained on all accessible surfaces of the stack previously covered by the first coating layer, preferably a first layer made of parylene and / or polyimide; the second layer is preferably an inorganic layer.
[0235] The growth of layers deposited by ALD is affected by the properties of the substrate. A layer deposited by ALD on a substrate with different regions having different chemical properties will have a non-uniform growth which will compromise the integrity of the second protective layer.
[0236] The deposition technology by ALD is particularly suitable for very tight and conformal coverage of surfaces with high roughness. This technology allows the realization of conformal layers that are free of defects such as holes (called "pinhole-free" layers) and behave as very good barrier layers. These conformal layers have extremely low WVTR coefficients. The WVTR coefficient (water vapor transmission rate) allows the evaluation of the vapor permeability of the packaging system. The lower the WVTR coefficient, the tighter the packaging system. For example, a 100 nm thick Al2O3 layer deposited by ALD has a vapor permeability of 0.00034 g / m 2 .d. The second coating may be made of a ceramic material, a glassy material or a glass-ceramic material, for example in oxide form, Al2O3 type, nitride, phosphate, oxynitride or siloxane. The thickness of the second coating is less than 200 nm, preferably 5 nm to 200 nm, more preferably 10 nm to 100 nm, 10 nm to 50 nm, even more preferably about 50 nm. Conformal deposition techniques are preferred, such as atomic layer deposition (ALD).
[0237] This second coating, which is deposited by ALD on the first polymer layer, ensures the tightness of the structure on the one hand, i.e. prevents water migration within the structure, and protects the first coating from atmospheric (especially air and humidity), thermal exposure, and thus prevents its degradation, on the other hand, wherein the first coating is preferably made of Parylene and / or polyimide, preferably of type F Parylene. This second layer prolongs the service life of the encapsulated battery.
[0238] However, these layers deposited by ALD are very fragile in terms of mechanical properties and require a rigid supporting surface to ensure the protective function of these layers. Depositing fragile layers on flexible surfaces can lead to the formation of cracks, thereby compromising the integrity of the protective layer.
[0239] Advantageously, a third coating layer is deposited on the second coating layer or on the packaging system 30, wherein the packaging system 30 is formed by a stack of several layers as described above, i.e., by a sequence, preferably a z-sequence of the packaging system, z≥1, to increase the protection of the battery cell from its external environment. Typically, the third layer is made of a polymer, such as silicone (e.g., deposited from hexamethyldisiloxane (HMDSO) by impregnation or by plasma-assisted chemical vapor deposition), or epoxy, or polyimide, or Parylene.
[0240] In addition, as described above, the packaging system may include layers of Parylene and / or polyimide (preferably about 3 μm thick) and layers containing electrically insulating materials (e.g., inorganic layers) conformally deposited by ALD that alternate in sequence, thereby manufacturing a multilayer packaging system. In order to improve the performance of the package, the packaging system may include a first layer made of Parylene and / or polyimide with a thickness of about 3 μm, a second layer containing electrically insulating materials (preferably an inorganic layer) conformally deposited on the first layer by ALD, a third layer made of Parylene and / or polyimide with a thickness of preferably about 3 μm deposited on the second layer, and a fourth layer containing electrically insulating materials conformally deposited on the third layer by ALD.
[0241] The cells or components thus packaged in the packaging system sequence, preferably the z-sequence, can then be covered with a final coating, thereby mechanically protecting the stack thus packaged and optionally making it aesthetically pleasing. The final coating protects the cells and prolongs their service life. Advantageously, the final coating is selected to withstand high temperatures and has a mechanical resistance sufficient to protect the cells during later use. Advantageously, the thickness of the final coating is from 1 μm to 50 μm. Ideally, the thickness of the final coating is from about 10 μm to 15 μm, a thickness range that protects the cells from mechanical damage.
[0242] Advantageously, a final coating is deposited on the packaging system formed by a stack of several layers, ie a sequence of packaging systems, preferably a z-sequence, z≥1; preferably, the final coating is deposited on a succession of layers, preferably about 3 μm thick, made of parylene and / or polyimide, and inorganic layers deposited conformally by ALD, in order to increase the protection of the cell from its external environment and from mechanical damage. Preferably, the thickness of this final packaging layer is about 10 to 15 μm.
[0243] The last coating is preferably based on epoxy resin, polyethylene naphthalate (PEN), polyimide, polyamide, polyurethane, silicone, sol-gel silicon or organosilicon. Advantageously, the last coating is deposited by dipping. Typically, the last layer is made of a polymer, such as silicone (for example, deposited by hexamethyldisiloxane (HMDSO) by dipping or by plasma-assisted chemical vapor deposition), or epoxy resin, or polyimide, or parylene. For example, a silicone layer (typically with a thickness of about 15 μm) can be deposited by injection to protect the battery from mechanical damage. The choice of this material stems from its high temperature resistance, so it is easy to assemble the battery by soldering on a circuit board without glass transition. Advantageously, the battery is encapsulated on four of the six faces of the stack. The encapsulation layer surrounds the periphery of the stack, and the remaining protection against the atmosphere is provided by the layer obtained by the terminals.
[0244] After the packaging step, the packaged stack is then cut according to the cutting planes so that the unit cell components can be obtained, and the anode connector 50 and the cathode connector 50 of the battery are exposed on each cutting plane, so that the packaging system 30 covers four of the six faces of the battery, preferably continuously, so that the system can be assembled without welding, and the other two faces of the battery are later covered by the terminal 40.
[0245] In an advantageous embodiment, the stack thus packaged and cut can be impregnated with a phase carrying lithium ions in an anhydrous environment, wherein the phase carrying lithium ions is, for example, an ionic liquid containing a lithium salt, which can be diluted with an organic solvent or a mixture of organic solvents containing a lithium salt, and the lithium salt in the organic solvent can be different from the lithium salt dissolved in the ionic liquid, as shown in paragraph 10 of the present application. The impregnation can be carried out by immersion in an electrolyte, wherein the electrolyte is, for example, an ionic liquid containing a lithium salt, which can be diluted with an organic solvent or a mixture of organic solvents containing a lithium salt, and the lithium salt in the organic solvent can be different from the lithium salt dissolved in the ionic liquid. Under capillary action, the ionic liquid immediately enters the pores.
[0246] After the packaging, cutting and possible impregnation steps of the cells, the terminals 40 are added to establish the electrical contacts required for proper functioning of the cells.
[0247] 6. terminal
[0248] Advantageously, the battery includes a terminal 40 where the cathode or anode, current collector, emerges. Preferably, the anode and cathode connectors are located on opposite sides of the stack.
[0249] A terminal system 40 is deposited on and around these connections 50. The connections can be metallized using plasma deposition techniques known to those skilled in the art, preferably by ALD and / or immersion in a bath of conductive epoxy embedded with silver and / or tin. Preferably, the terminals are formed by a stack of layers comprising, in sequence: a conductive coating, preferably a metal layer, deposited by ALD; a second epoxy layer embedded with silver deposited on the first layer; and a third layer based on tin deposited on the second layer. The first conductive layer deposited by ALD serves to protect the cross section of the battery from moisture. This first conductive layer deposited by ALD is optional. This first conductive layer can extend the calendar life of the battery by reducing the WVTR at the terminals. This first thin coating can in particular be a metal layer, or based on a metal nitride. The second layer made of epoxy embedded with silver makes the connections "flexible" without breaking the electrical contact when the circuit is subjected to thermal and / or vibration stresses.
[0250] A third metallization layer based on tin is used to ensure the solderability of the component.
[0251] In another embodiment, the third layer may include two layers of different materials. The first layer is in contact with the epoxy layer embedded with silver. This layer is made of nickel and is deposited by electrodeposition. The nickel layer acts as a thermal barrier and protects the remaining components from diffusion during the assembly step by remelting. The final layer deposited on the nickel layer is also a metallization layer, which is preferably made of tin to make the interface compatible with the assembly by remelting. The tin layer can be deposited by immersion in a tin bath or by electrodeposition; these techniques are well known.
[0252] For some components located on copper lines obtained by microwiring, it may be necessary to have a final metallization layer made of copper. This layer can be achieved by electrodeposition instead of tin.
[0253] In another embodiment, the terminal 40 may be formed from a stack of layers comprising, in sequence, a layer made of epoxy resin embedded with silver, and a second layer based on tin or nickel deposited on the first layer.
[0254] In another embodiment, the terminal 40 may be formed from a stack of layers comprising, in order: a conductive polymer layer, such as a silver embedded epoxy layer; a second layer based on nickel deposited on the first layer; and a third layer based on tin or copper.
[0255] In a preferred embodiment, the terminal 40 may be formed of different layers, which are, in a non-limiting manner, a conductive polymer layer such as an epoxy layer embedded with silver, a nickel layer, or a tin layer.
[0256] In another preferred embodiment, at the edge of the cathode and anode connectors, the terminal 40 is formed by a first stack of layers, which in turn comprises a first layer made of a graphite-embedded material, preferably an epoxy resin embedded with graphite, and a second layer deposited on the first layer, comprising metallic copper obtained from an ink embedded with copper nanoparticles. This first stack of terminals is then sintered by an infrared flash lamp, so as to obtain a coating of the cathode and anode connectors with a metallic copper layer.
[0257] Depending on the final use of the battery, the terminal may also include a second stack of layers arranged on the first stack of the terminal, the second stack comprising in sequence: a first layer of a tin-zinc alloy, preferably deposited by immersion in a molten tin-zinc bath, so as to ensure the compactness of the battery at the lowest cost; and a second layer based on pure tin deposited by electrodeposition, or comprising a second layer based on an alloy with silver, palladium and copper, which second layer is deposited on the first layer of the second stack.
[0258] The terminals allow for alternating positive and negative electrical connections at each end of the battery. These terminals 40 allow for parallel electrical connections to be established between the different battery elements. Thus, only the cathode connector 50 is present at one end, and only the anode connector 50 is present at the other end. Advantageously, the anode connector 50 and the cathode connector 50 are located on opposite sides of the stack.
[0259] Advantageously, after step (11) of the method for manufacturing a lithium-ion battery according to the present invention:
[0260] - The following layers are deposited alternately in sequence on the impregnated structure:
[0261] ■ at least one first layer of Parylene and / or polyimide on the cell,
[0262] ■ at least one second layer comprising an electrically insulating material deposited on said first layer of Parylene and / or polyimide by ALD (Atomic Layer Deposition),
[0263] ■ depositing a layer on the at least one first layer and the at least one second layer, which alternate in sequence, so as to protect the battery from mechanical damage to the battery, the layer preferably being made of silicone, epoxy, or polyimide, or Parylene, so as to form a packaging system for the battery,
[0264] - cutting the encapsulated impregnated structure along two cutting planes, so that the anodic and cathodic connectors of the cell are exposed on each cutting plane, so that the encapsulation system covers four of the six faces of the cell, preferably continuously, so as to obtain a unit cell,
[0265] - The following layers are sequentially deposited on and around these anodic and cathodic connectors:
[0266] ■ Optionally, a first conductive layer, preferably deposited by ALD,
[0267] ■ a second layer based on silver embedded epoxy deposited on the first conductive layer, and
[0268] ■ a third layer based on nickel deposited on the second layer, and
[0269] ■ A fourth layer based on tin or copper deposited on the third layer.
[0270] In another preferred embodiment, a lithium ion battery according to the present invention is manufactured by a method comprising the following steps:
[0271] (1) a) providing a colloidal suspension comprising aggregates or agglomerates of nanoparticles of at least one cathode material, wherein the average primary diameter D of the nanoparticles is 50 Less than or equal to 50nm;
[0272] b) providing a colloidal suspension comprising aggregates or agglomerates of nanoparticles of at least one anode material, the nanoparticles having an average primary diameter D 50 Less than or equal to 50nm;
[0273] c) providing two flat conductive substrates, preferably metal substrates, which can be used as current collectors for the battery,
[0274] (2) depositing at least one cathode layer or an anode layer on the substrate provided in step (1) from a suspension of nanoparticles of the material provided in step (1) or step (2) by dip coating, by ink jetting, by doctor blade, by roller coating, by curtain coating or by electrophoresis, preferably by pulsed current constant current electrodeposition,
[0275] (3) drying the layer obtained in step (2),
[0276] (4) optionally, depositing a layer of electrically insulating material on or inside the holes of the cathode layer and / or anode layer in step (3) by ALD,
[0277] (5) Preferably, the average primary diameter D is obtained by electrophoresis, by inkjet, by doctor blade, by roller coating, by curtain coating or by dip coating. 50 Less than or equal to 50nm and average diameter D 50 A colloidal suspension of nanoparticles of the aggregated material or agglomerated material having a size of about 100 nm is deposited on the cathode layer or anode layer obtained in step (3) and / or step (4) with a film of an electrically insulating material or an ion-conducting material or an electrically insulating material capable of ion conduction, preferably a porous film, preferably a mesoporous film,
[0278] (6) drying the layer obtained in step (5),
[0279] (7) realizing a stack comprising alternating cathode layers and anode layers, wherein the cathode layers and the anode layers are preferably offset in the transverse direction,
[0280] (8) hot pressing the anode layer and cathode layer obtained in step (7) so as to be juxtaposed with the membrane present on the anode layer and cathode layer obtained in step (8) and obtaining an assembled stack,
[0281] (9) Optionally, depositing a layer of electrically insulating material by ALD over and inside the pores of the assembled stack.
[0282] The order of steps (1a), (1b) and (1c) is not important.
[0283] Compared with depositing the electrically insulating material layer in step (4), it is preferred to deposit the electrically insulating material layer on the assembled stack obtained in step (8) by ALD; compared with depositing the electrically insulating material layer on each electrode separately, it is simpler to deposit the electrically insulating material layer on the stack that has been thermally assembled or hot pressed by ALD.
[0284] After step (8) or after step (9) of the method for manufacturing a lithium ion battery according to the present invention:
[0285] - depositing a packaging system alternately in sequence on the assembled stack, the packaging system being formed by a series of layers, i.e. a sequence, preferably a z-sequence, comprising:
[0286] ■ a first coating deposited on the assembled stack, the first coating preferably being selected from Parylene, Parylene F-type, polyimide, epoxy resin, silicone resin, polyamide and / or mixtures thereof,
[0287] ■ a second coating layer deposited on the first coating layer by atomic layer deposition, the second coating layer comprising an electrically insulating material,
[0288] ■ the sequence may be repeated z times, z ≥ 1, - depositing a final coating on the series of layers, the final coating being made of a material selected from epoxy resin, polyethylene naphthalate (PEN), polyimide, polyamide, polyurethane, silicone, sol-gel silicone or organosilicon,
[0289] - then cutting the encapsulated assembled stack along two cutting planes, exposing the anode connector and the cathode connector of the assembled stack on each cutting plane, so that the encapsulation system covers four of the six faces of the assembled stack, preferably continuously, thereby obtaining a unit cell,
[0290] - impregnating the packaged and cut unit cells with a phase loaded with lithium ions,
[0291] - On and around these anodic and cathodic connectors are sequentially deposited:
[0292] ■ a first layer of graphite-embedded material, preferably a graphite-embedded epoxy resin,
[0293] ■ A second layer deposited on the first layer containing metallic copper obtained from an ink comprising nanoparticles of copper.
[0294] - subjecting the obtained layer to a heat treatment, preferably by means of an infrared flash lamp, so as to obtain a covering of the cathode and anode connectors with a metallic copper layer,
[0295] A second stack may be deposited sequentially on and around the first stack of terminals, the second stack comprising:
[0296] ■ a first layer made of a tin-zinc alloy, preferably deposited by immersion in a tin-zinc molten bath, in order to ensure the compactness of the cell at a minimum cost; and
[0297] ■ A second layer based on pure tin, or comprising an alloy with silver, palladium and copper, deposited by electrodeposition, which second layer is deposited on the first layer of the second stack.
[0298] Advantageously, the anode and cathode connections are located on opposite sides of the stack.
[0299] All embodiments relating to the deposition of the dielectric layer shown in section 5, the assembly of the cells, the impregnation of the assembled cells, the packaging system and the deposition of the above-mentioned terminals can be combined independently of each other if such a combination is feasible for a person skilled in the art.
[0300] Example
[0301] Example 1 : Obtaining a mesoporous cathode based on LiMn2O4
[0302] A suspension of nanoparticles of LiMn2O4 was prepared by hydrothermal synthesis: 14.85 g of LiOH, H2O was dissolved in 500 ml of water. 43.1 g of KMnO4 was added to the solution, and the liquid phase was poured into an autoclave. 28 ml of isobutyraldehyde and water were added under stirring until the volume reached 3.54 L. The autoclave was then heated to 180°C and kept at this temperature for 6 hours. After slow cooling, a black precipitate suspended in the solvent was obtained. The precipitate was subjected to a series of centrifugation-redispersion steps in water until an aggregated suspension with a conductivity of about 300 μS / cm and a zeta potential of -30 mV was obtained. The size of the primary particles was very uniform (monodispersed), about 10 nm to 20 nm, and the size of the aggregates was 100 nm to 200 nm. The product was characterized by X-ray diffraction and electron microscopy.
[0303] These aggregates were deposited in a stainless steel foil (316L) with a thickness of 5 μm by electrophoresis in an aqueous medium, by applying a pulsed current with a peak value of 0.6 A and an average value of 0.2 A and a voltage of about 4 V to 6 V for 400 seconds. A deposit with a thickness of about 4 μm was thus obtained. The deposit was dried in a temperature and humidity controlled oven to prevent crack formation during drying.
[0304] The deposit was consolidated in air at 600°C for 1 hour to fuse the nanoparticles together, improve adhesion to the substrate, and complete the recrystallization of LiMn2O4. The open porosity of the layer was about 45% by volume, with pore sizes ranging from 10 nm to 20 nm (see below, Example 5).
[0305] In an alternative to the method, a stable monodisperse colloidal suspension is obtained with a particle size of 20 nm to 30 nm and a zeta potential of about 55 mV. In order to obtain aggregates of a defined size, a solution of LiOH is added to stabilize the suspension until aggregates of a size of about 100 nm are obtained; the zeta potential of the suspension is now 35 mV and its conductivity increases by several hundred μS / cm. This colloidal suspension is used to deposit a layer of 4 μm thickness on a 5 μm thick stainless steel foil (316L) by electrophoresis. The distance between the electrode and the counter electrode is about 1 cm and the current density is about 6 mA / cm 2 The duration of the current pulses was 5 ms and the time between pulses was 1 ms. Drying and consolidation were carried out as described above.
[0306] It should be noted that in this example, the colloidal suspension naturally contains aggregates due to the residual ionic charge. If further purification is carried out by further steps of centrifugation and / or ultrafiltration techniques, a stable monodisperse suspension with a conductivity of less than 100 μS / cm is obtained. This suspension does not contain aggregates and can therefore be used in the electrophoresis step. The suspension needs to be destabilized by adding LiOH.
[0307] Example 2 : Obtaining a mesoporous cathode based on LiCoO2
[0308] A suspension of crystalline nanoparticles of LiCoO2 was prepared by hydrothermal synthesis. For 100 ml of the suspension, 20 ml of 0.5 M aqueous cobalt nitrate hexahydrate was added to 20 ml of 3 M lithium hydroxide monohydrate solution under stirring, followed by dropwise addition of 20 ml of 50% H2O2. The reaction mixture was placed in an autoclave at 200°C for 1 hour; the pressure in the autoclave reached about 15 bar.
[0309] A black precipitate suspended in a solvent is obtained. This precipitate is subjected to a series of centrifugation-redispersion steps in water until a suspension having a conductivity of about 200 μS / cm and a zeta potential of -30 mV is obtained. The size of the primary particles is about 10 nm to 20 nm, and the size of the aggregates is 100 nm to 200 nm. The product is characterized by X-ray diffraction and electron microscopy.
[0310] These aggregates were deposited in a stainless steel foil with a thickness of 5 μm by electrophoresis in an aqueous medium, by applying a pulsed current with a peak value of 0.6 A and an average value of 0.2 A and a voltage of about 4 V to 6 V for 400 seconds. A deposit with a thickness of about 4 μm was thus obtained. The deposit was consolidated at 600°C in air for 1 hour to fuse the nanoparticles together, to improve adhesion to the substrate, and to complete the recrystallization of LiCoO2.
[0311] Example 3 :Obtain Li4Ti5O-based 12 Mesoporous anode
[0312] Preparation of Li4Ti5O by glycothermal synthesis 12Suspension of nanoparticles: 190 ml of 1,4-butanediol is poured into a beaker and 4.25 g of lithium acetate is added under stirring. The solution is kept stirring until the acetate is completely dissolved. 16.9 g of tetrabutyl titanate is taken under an inert atmosphere and introduced into the acetate solution. The solution is stirred for several minutes and then transferred to an autoclave, which is pre-filled with an additional 60 ml of butanediol. The autoclave is then closed and purged with nitrogen for at least 10 minutes. The autoclave is then heated to 300°C at a rate of 3°C / min under stirring and maintained at this temperature for 2 hours. At the end, it is allowed to cool, still under stirring.
[0313] A white precipitate suspended in a solvent is obtained. A series of centrifugation-redispersion steps are carried out on the precipitate in ethanol until a pure colloidal suspension with low conductivity is obtained. The colloidal suspension contains aggregates of about 150 nm formed by primary particles of 10 nm. The zeta potential is about -45 mV. The product is characterized by X-ray diffraction and electron microscopy. FIG. 1 (a) shows a diffraction pattern, and FIG. 1 (b) shows a photograph obtained by transmission electron microscopy of primary nanoparticles.
[0314] These aggregates were deposited in a stainless steel foil with a thickness of 5 μm by electrophoresis in an aqueous medium by applying a pulsed current with a peak value of 0.6 A and an average value of 0.2 A and a voltage of about 3 V to 5 V for 500 seconds. A deposit with a thickness of about 4 μm was thus obtained. The deposit was consolidated by RTA annealing at 40% power in nitrogen for 1 hour to fuse the nanoparticles together to improve adhesion to the substrate and to make the Li4Ti5O 12 The recrystallization is more perfect.
[0315] Example 4 : Coating on mesoporous electrode obtained by ALD (case of aluminum oxide deposition on cathode)
[0316] In an ALD P300B reactor (supplier: Picosun), thin layers of aluminum oxide were deposited at 180° C. at an argon pressure of 2 mbar. Here, argon was used simultaneously as carrier gas and for purging. Before each deposition, a drying time of 3 hours was used. The precursors used were water and TMA (trimethylaluminum). The deposition cycle consisted of the following steps:
[0317] - TMA injection for 200 ms
[0318] - Purge the chamber with Ar for 6 seconds
[0319] -Inject water for 50 milliseconds
[0320] - Purge the chamber with Ar for 6 seconds
[0321] 14 cycles were performed to reach a coating thickness of 1.6 nm. After these different cycles, vacuum drying was performed at 120° C. for 12 hours to remove the reagent residues on the surface.
[0322] Example 5 : Determination of specific surface area and pore volume
[0323] The specific surface area of the LiMn2O4 layer (abbreviated as "LMO") obtained by a method similar to that described in Example 1 above was determined by the BET technique (Brunauer-Emmett-Teller) known to those skilled in the art. The sample was an annealed deposit of LMO with a thickness of 2 μm deposited on each of the two faces of a stainless steel foil (thickness of 5 μm), with a grammage of 0.6 mg / cm per face. 2 (or the weight of both sides is 1.2mg / cm 2 ). Two 5×10 cm sheets were laser cut, rolled around each other, and inserted into the glass cell of the BET apparatus. The adsorption gas used for the analysis was N2. The results are as follows:
[0324] Total mass of sample (foil + sediment): 0.512 g
[0325] Sediment mass (m): 0.120g
[0326] Deposition mass after 5 hours at 150°C in vacuum: 0.117 g
[0327] Specific surface area BET(S): 43.80m 2 / g
[0328] Pore volume (V): 0.2016cm 3 / g
[0329] Aperture (D = 4V / A): 20nm
[0330] The BET method can only characterize open pores with a diameter less than 50 nm (the pore size is calculated by considering the pores as cylindrical). The estimation of open pores with a size greater than 50 nm requires the use of other methods (mercury intrusion porosimetry). However, it can be noted that this limiting diameter corresponds to the maximum pore size of the hydrothermal LMO deposit measured in the FIB. The specific surface area of the LMO powder obtained by the hydrothermal synthesis method is 160 m 2 / g(to be determined separately).
[0331] Assume that the impregnation diameter is 18 mm and the LMO weight is 0.6 mg / cm 2 To fill the entire accessible pore space of the El-Cell disk electrode, a volume of 2.3 μL of electrolyte would be required. The theoretical density of LMO is d LMOEqual to 4.29g / cm 3 The porosity is equivalent to the void volume divided by the total volume occupied by the sediment, resulting in the following ratio:
[0332]
[0333] The porosity obtained by this calculation (46.4%) is very close to the porosity estimated by measuring the mass of the sediment and its average thickness (40% to 50%).
[0334] It can therefore be concluded that the pores in the LMO layer deposited by the method according to the invention are mostly open pores.
[0335] Example 6 : Manufacturing a battery using the electrode according to the present invention
[0336] Several anodes or cathodes in the form of thin layers were obtained according to Example 3 or Example 2. These electrodes were covered with a porous layer obtained from a suspension of nanoparticles of Li3PO4 as shown below.
[0337] a. Obtaining a suspension of Li3PO4 nanoparticles
[0338] Prepare two solutions:
[0339] 11.44 g of CH3COOLi,2H2O were dissolved in 112 ml of water, and then 56 ml of water were added to the medium under vigorous stirring to obtain solution A.
[0340] 4.0584 g of H3PO4 was diluted in 105.6 ml of water, and then 45.6 ml of ethanol was added to the solution to obtain a second solution, hereinafter referred to as solution B.
[0341] Solution B was then added to solution A with vigorous stirring.
[0342] After the bubbles formed during mixing disappear, the resulting solution is very clear and TM This solution was added to 1.2 liters of acetone using a homogenizer of the CEVA® type in order to homogenize the medium. A white precipitate was immediately observed in the suspension, which was located in the liquid phase.
[0343] Under magnetic stirring, the reaction medium is homogenized for 5 minutes, and then kept for 10 minutes. The reaction medium is left to stand for decantation for 1 to 2 hours. The supernatant is discarded, and the remaining suspension is then centrifuged at 6000rpm for 10 minutes. Then 300ml of water is added to put the precipitate back into the suspension (using ultrasonic generator, magnetic stirring). Under vigorous stirring, 125ml of 100g / l sodium triphosphate solution is added to the obtained colloidal suspension. Therefore, the suspension becomes more stable. Then an ultrasonic generator is used to sonicate the suspension. Then the suspension is centrifuged at 8000rpm for 15 minutes. Then the precipitate is dispersed again in the water of 150ml. Subsequently, the obtained suspension is centrifuged again at 8000rpm for 15 minutes, and the obtained precipitate is dispersed again in the ethanol of 300ml, to obtain a suspension that can be electrophoretically deposited.
[0344] Agglomerates of approximately 100 nm were thus obtained in suspension in ethanol, formed from 10 nm Li3PO4 primary particles.
[0345] b. A porous layer formed by a suspension of Li3PO4 nanoparticles described in section a) above is placed on the previously formed anode layer and cathode layer
[0346] A thin porous layer of Li3PO4 was then deposited on the surface of the previously formed anode and cathode by electrophoresis, by applying an electric field of 20 V / cm for 90 seconds to the suspension of nanoparticles of Li3PO4 obtained as above, in order to obtain a layer of 1.5 μm. The layer was then dried at 120° C. in air, and the previously dried layer was then subjected to a calcination treatment at 350° C. for 60 minutes to remove any traces of organic residues.
[0347] c. Fabrication of electrochemical cells
[0348] On the electrode LiCoO2 obtained according to Example 2, and on the electrode Li4Ti5O obtained according to Example 3 12 After depositing 1.5 μm porous Li3PO4 on the substrate, the two subsystems were stacked in such a way that the Li3PO4 films were in contact. The stack was then vacuum hot-pressed.
[0349] To this end, the stack was placed under a pressure of 1.5 MPa and then -3 The stack was then hot-pressed at 450°C for 1 minute at a pressure of 45 MPa, and the system was then cooled to ambient temperature.
[0350] Once assembled, a rigid multilayer system formed by the assembled unit cells is obtained.
[0351] The assembly was then immersed in a 0.7 M electrolyte containing PYR14TFSI and LiTFSI. The ionic liquid quickly entered the pores by capillary action. The system remained immersed for 1 minute, and then the surface of the stack of unit cells was dried by a N2 curtain.
[0352] d. Obtaining a battery comprising a plurality of electrochemical unit cells
[0353] Several anodes or cathodes in the form of thin layers were obtained according to Example 3 or Example 2. These electrodes were covered with a porous layer obtained from a suspension of nanoparticles of Li3PO4, as shown below.
[0354] In each of the preformed electrodes (LiCoO2 and Li4Ti5O 12 ) and then stacked the two subsystems in such a way that the Li3PO4 films were in contact. The stack, which includes cathodes and anodes in the form of thin layers alternately covered with porous layers, was then vacuum hot-pressed, and the Li3PO4 films of the cathode and anode were in contact.
[0355] To this end, the stack was placed under a pressure of 1.5 MPa and then -3 The stack was then hot-pressed at 450°C for 1 minute at a pressure of 45 MPa, and the system was then cooled to ambient temperature.
[0356] Once assembled, a rigid multilayer system is obtained, formed from several assembled unit cells.
[0357] The assembly was then immersed in a 0.7 M electrolyte containing PYR14TFSI and LiTFSI. The ionic liquid quickly entered the pores by capillary action. The system remained immersed for 1 minute, and then the surface of the stack of unit cells was dried by a N2 curtain.
[0358] A lithium-ion battery is thereby obtained which comprises several electrochemical cells, each of which comprises an electrode according to the invention.
Claims
1. A method for manufacturing a porous electrode, the electrode comprising a layer deposited on a substrate, the layer being binder-free and having a porosity greater than 30% by volume and pores with an average diameter of less than 50 nm, the method being characterized in that: (a) providing a colloidal suspension comprising aggregates or agglomerates of nanoparticles of at least one material P, wherein the average primary diameter D of the nanoparticles is 50 Less than or equal to 80nm, the average diameter of the aggregates or agglomerates is 80nm to 300nm, (b) providing a substrate, (c) depositing a porous electrode layer on the substrate from the colloidal suspension provided in step (a) by electrophoresis, by inkjet, by doctor blade, by roll coating, by curtain coating or by dip coating, (d) drying the layer obtained in step (c).
2. The method for manufacturing a porous electrode according to claim 1, wherein: (a1) providing a colloidal suspension comprising nanoparticles of at least one material P, The primary diameter D of the nanoparticles 50 Less than or equal to 80nm; (a2) destabilizing the nanoparticles present in the colloidal suspension so as to form aggregates or agglomerates of particles with an average diameter of 80 nm to 300 nm; (b) providing a substrate; (c) depositing a mesoporous electrode layer on the substrate from the colloidal suspension comprising aggregates or agglomerates of nanoparticles obtained in step (a2) by electrophoresis, by inkjet, by doctor blade, by roll coating, by curtain coating or by dip coating; (d) drying the layer.
3. The method according to claim 2, wherein in step (a2), the nanoparticles are destabilized by adding a destabilizing agent.
4. The method according to claim 3, wherein the destabilizing agent is a salt.
5. The method according to claim 4, wherein the salt is LiOH.
6. The method according to claim 1, comprising a step (e) of consolidating the porous electrode layer obtained in step (d) by pressing and / or heating.
7. The method according to claim 1 or 2, wherein the thickness of the deposit obtained in step (c) is less than 10 μm.
8. The method according to claim 1 or 2, wherein the diameter of the nanoparticles is 10 nm to 50 nm.
9. The method according to claim 1 or 2, wherein the average diameter of the pores is 2 nm to 80 nm.
10. The method according to claim 1 or 2, wherein the porosity of the porous electrode is 35% to 50% by volume.
11. The method according to claim 1 or 2, wherein the electrode is a cathode and the material P is selected from the group consisting of: Oxide: LiMn2O4; Li 1+x Mn 2-x O4, where 0 <x<0.15;LiCoO2; LiNiO2; LiMn 1.5 Ni 0.5 O4; LiMn 1.5 Ni 0.5-x X x O4, wherein X is selected from Al, Fe, Cr, Co, Rh, Nd, Sc, Y, Lu, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and 0 <x<0.1;LiMn 2-x M x O4, where M = Er, Dy, Gd, Tb, Yb, Al, Y, Ni, Co, Ti, Sn, As, Mg or a mixture of these compounds, and wherein 0 <x<0.4;LiFeO2;LiMn 1 / 3 Ni 1 / 3Co 1 / 3 O2; LiNi 0.8 Co 0.15 Al 0.05 O2; LiAl x Mn 2-x O4, where 0≤x<0.15; LiNi 1 / x Co 1 / y Mn 1 / z O2, where x+y+z=10; phosphates LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3; phosphates of the formula LiMM’PO4, where M and M’ are different and are selected from Fe, Mn, Ni, Co, V; All lithium forms the following chalcogenides: V2O5, V3O8, TiS2, titanium oxysulfide TiO y S z , where z = 2-y and 0.3≤y≤1, tungsten oxysulfide WO y S z , where 0.6 < y < 3 and 0.1 < z < 2, CuS, CuS2.
12. The method according to claim 1 or 2, wherein the electrode is an anode and the material P is selected from the group consisting of: carbon nanotubes, graphene, graphite; lithium iron phosphate of the typical molecular formula LiFePO4; The typical molecular formula is Si a Sn b O y N z of silicon tin oxynitride, where a > 0, b > 0, a + b ≤ 2, 0 < y ≤ 4, 0 < z ≤ 3, also known as SiTON, SiSn 0.87 O 1.2 N 1.72 ; and carbon oxynitride, with the typical molecular formula Si a Sn b C c O y N z , where a > 0, b > 0, a + b ≤ 2, 0 < c < 10, 0 < y < 24, 0 < z < 17; Si x N y Type nitride; Sn x N y Type nitride; Zn x N y Type nitride; Li 3-x M x N-type nitride, where M = Co, 0 ≤ x ≤ 0.5, M = Ni, 0 ≤ x ≤ 0.6, M = Cu, 0 ≤ x ≤ 0.3; Si 3-x M x N4 type nitride, where M = Co or Fe, and 0≤x≤3; Oxides SnO2, SnO, Li2SnO3, SnSiO3, Li x SiO y Where x>=0 and 2>y>0, Li4Ti5O 12 、TiNb2O7、Co3O4、SnB 0.6 P 0.4 O 2.9 and TiO2; the composite oxide TiNb2O7, which contains 0 wt% to 10 wt% carbon.
13. The method according to claim 1 or 6, wherein after step (d) or step (e), in step (f) a layer of electrically insulating material is deposited on or inside the pores of the porous electrode layer.
14. The method according to claim 13, wherein the electrically insulating material is selected from the group consisting of Al2O3, SiO2, and ZrO2.
15. The method according to claim 1 or 6, wherein after step (d) or after step (e), in step (f), a layer of ion conductive material is deposited on or inside the pores of the porous electrode layer, and the ion conductive material is selected from Li3PO4, Li3BO3, and lithium lanthanum zirconium oxide.
16. Use of the method according to claim 1 or 6 in the manufacture of electronic, electrical or electrotechnical devices.
17. Use of the method according to claim 16 for manufacturing a porous electrode in a device selected from the group consisting of: a battery, a capacitor, a supercapacitor, a capacitor, a resistor, an inductor, a transistor, a photovoltaic cell.
18. A method for manufacturing a battery, which implements the method for manufacturing a porous electrode according to claim 1 or 6.
19. The method for manufacturing a battery according to claim 18, comprising the steps of: (1) providing a colloidal suspension comprising aggregates or agglomerates of nanoparticles of at least one cathode material, wherein the average primary diameter D of the nanoparticles of the cathode material is 50 Less than or equal to 50nm; (2) providing a colloidal suspension comprising aggregates or agglomerates of nanoparticles of at least one anode material, wherein the average primary diameter D of the nanoparticles of the anode material is 50 Less than or equal to 50nm; (3) providing at least two flat conductive substrates, (4) depositing at least one cathode layer or an anode layer on the substrate provided in step (3) from a suspension of nanoparticles of the material provided in step (1) or step (2) by dip coating, by ink jetting, by doctor blade, by roller coating, by curtain coating or by electrophoresis, (5) drying the layer obtained in step (4), or (5) drying the layer obtained in step (4), and (6) depositing a layer of an electrically insulating material on or inside the holes of the cathode layer and / or anode layer obtained in step (5) by ALD, (7) From the average primary diameter D 50 Less than or equal to 50nm and average diameter D 50 A colloidal suspension of aggregates or agglomerates of the nanoparticles having a diameter of 100 nm is prepared, and an electrically insulating material or an ion conductive material or an electrically insulating material film capable of ion conduction is deposited on the cathode layer or the anode layer obtained in step (5) or step (6), (8) drying the layer obtained in step (7), (9) obtaining a stack comprising alternating cathode layers and anode layers, (10) hot pressing the anode layer and cathode layer obtained in step (9) so as to be juxtaposed with the membrane present on the anode layer and cathode layer obtained in step (8) and obtaining an assembled stack, (11) impregnating the structure obtained in step (10) with a phase loaded with lithium ions, An impregnated structure is thus obtained.
20. The method of claim 19, wherein between steps 10 and 11: - depositing, in turn and alternately on the assembled stack, a packaging system formed by a series of layers, i.e. a z-sequence, comprising: a first coating deposited on the assembled stack, the first coating being selected from Parylene, Parylene Type F, polyimide, epoxy resin, silicone resin, polyamide and / or mixtures thereof, a second coating layer deposited on the first coating layer by atomic layer deposition, the second coating layer comprising an electrically insulating material, The sequence is repeated z times, z ≥ 1, - depositing on this series of layers a final coating made of a material chosen among epoxy resins, polyethylene naphthalate PEN, polyimide, polyamide, polyurethane, silicone, sol-gel silicone or organosilicon, - cutting the packaged assembled stack along two cutting planes, exposing the anode connector and the cathode connector of the assembled stack on each cutting plane, so that the packaging system covers four of the six faces of the assembled stack, thereby obtaining a unit cell, and after step 11, - The following layers are sequentially deposited on and around these anodic and cathodic connectors: The first layer of graphite embedded material, a second layer deposited on said first layer and containing metallic copper obtained from an ink comprising nanoparticles of copper, - subjecting the obtained layer to a heat treatment, so as to obtain a covering of the cathode and anode connectors with a metallic copper layer.
21. The method according to claim 20, wherein the following layers are sequentially deposited on and around the metallic copper layer: - a first layer made of tin-zinc alloy, thus ensuring the tightness of the cell at minimal cost; and - A second layer based on pure tin, or comprising an alloy with silver, palladium and copper, deposited by electrodeposition, this second layer being deposited on the first layer of tin-zinc alloy.
22. The method of claim 20, wherein the anode connector and the cathode connector are located on opposite sides of the stack.
23. A porous electrode having a porosity greater than 30% by volume, comprising pores with an average pore size less than 80 nm and a primary particle size less than 30 nm, characterized in that: the thickness of the porous electrode is less than 100 μm, and the porous electrode does not contain a binder.
24. The porous electrode according to claim 23, characterized in that The pores are impregnated with an electrolyte.
25. The porous electrode according to claim 24, characterized in that The electrolyte is an ionic liquid containing a lithium salt, the ionic liquid is diluted or undiluted by an organic solvent or a mixture of organic solvents containing a lithium salt, and the lithium salt in the organic solvent is the same as or different from the lithium salt dissolved in the ionic liquid.
26. The porous electrode according to claim 24, characterized in that The pores are impregnated with a lithium ion loaded phase comprising at least 50 wt % of at least one ionic liquid.
27. A battery comprising at least one porous electrode obtained by the method according to claim 1 or claim 6.
28. The battery according to claim 27, characterized in that All electrodes of the battery are A porous electrode obtained according to the method of claim 1 or claim 6.
Citation Information
Patent Citations
Method for the production of electrodes for fully solid batteries
EP2774194B1
Lithium-ion battery containing an electrolyte comprising an ionic liquid
US20100209783A1
Mesoporous network electrode for electrochemical cell
WO2002075826A2
Method for manufacturing all-solid-state thin-film batteries
WO2013064779A1
Fully solid thin-film batteries and method for producing fully solid thin-film batteries
WO2013064781A1